Composition, transfer film, method for producing laminate, laminate, and method for producing semiconductor package
By using a composition containing resin X and filler, and adding armal alkaline agent and photocopy of the optical agglomeration to the resin X, the sensitivity resin composition in the existing technology is prone to cracking in the circulating heat test, realizing the realization, realizing the realization, realizing the realization, realizing the realization, realizing the realization, realizing the realization, realizing the realization, realizing the realization, realizing it, realizing it, realizing it, and realizing it. The excellent circulation thermal characteristics and stability of the membrane.
Patent Information
- Application Number
- CN202380047553.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-27
- Filing Date
- 2023-06-27
- Publication Date
- 2025-01-24
AI Technical Summary
The photosensitive resin composition used in the prior art is prone to cracks during the cyclic heat test, resulting in poor cyclic heat characteristics of the film.
A composition containing resin X and filler. Resin X includes polytamine anterior body, polytamide, polybenzene meal anterior body, and polyzhenyrazole. The average particle size is less than 300nm, and the thermal alkaline agent and the optical agglomeration agent are added to the resin X.
The membrane formed by this composition shows excellent circulating thermal characteristics in the cycle thermal test, reducing the occurrence of cracks, thereby improving the stability of the membrane and the service life.
Smart Images

Figure BDA0005190593490000101 
Figure BDA0005190593490000121 
Figure BDA0005190593490000131
Abstract
Description
Technical Field
[0001] The present invention relates to a composition, a transfer film, a method for manufacturing a laminate, a laminate and a method for manufacturing a semiconductor package.
[0002] In a display device having a touch panel such as an electrostatic capacitive input device (as a display device, for example, there are organic electroluminescent (EL) display devices and liquid crystal display devices, etc.), a conductive pattern including an electrode pattern of a sensor corresponding to a visual recognition portion, a peripheral wiring portion, and wiring of a lead-out wiring portion is provided inside the touch panel.
[0003] For example, Patent Document 1 discloses a photosensitive resin composition having a predetermined structure.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-103307 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] The present inventors have found that when a film is formed using a composition having a structure as described in Patent Document 1 and the obtained film is subjected to a cycle heat test of repeatedly heating and cooling, cracks are likely to occur in the film.
[0009] Hereinafter, the case where cracks are less likely to occur when the above-mentioned cyclic heat test is performed is also referred to as having excellent cyclic heat characteristics.
[0010] Therefore, an object of the present invention is to provide a composition capable of forming a film having excellent cyclic thermal characteristics.
[0011] Another object of the present invention is to provide a transfer film, a method for producing a laminate, a laminate, and a method for producing a semiconductor package related to the above-mentioned composition.
[0012] Means for solving technical problems
[0013] The present inventors have conducted intensive studies to solve the above-mentioned problems, and as a result, have found that the above-mentioned problems can be solved by the following configuration, thereby completing the present invention.
[0014] (1) A composition comprising a resin X and a filler, wherein the resin X comprises at least one selected from a polyimide precursor, a polyimide, a polybenzoxazole precursor and a polybenzoxazole,
[0015] The content of the filler is 50.0% by mass or more relative to the total solid content of the composition.
[0016] The average particle size of the filler calculated by the particle size measurement method described later is 300 nm or less.
[0017] (2) The composition according to (1), wherein the filler includes at least one selected from silicon dioxide, boron nitride, barium sulfate, and silicate.
[0018] (3) The composition according to (1) or (2), wherein the average particle size of the filler is 5 to 100 nm.
[0019] (4) The composition according to any one of (1) to (3), wherein the content of the filler is 60.0% by mass or more based on the total solid content of the composition.
[0020] (5) The composition according to any one of (1) to (4), wherein the filler is surface-treated with a surface modifier.
[0021] (6) The composition according to (5), wherein the content of the surface modifier is 3% by mass or less relative to the total mass of the filler.
[0022] (7) The composition according to (6), wherein the content of the surface modifier is 1% by mass or less relative to the total mass of the filler.
[0023] (8) The composition according to any one of (1) to (7), further comprising a thermal base generator,
[0024] Resin X comprises a precursor.
[0025] (9) The composition according to (8), wherein the mass ratio of the content of the thermal base generator to the content of the resin X is 0.10 or less.
[0026] (10) The composition according to (8) or (9), wherein the content of the thermal base generator is 5.0% by mass or less based on the total solid content of the composition.
[0027] (11) The composition according to any one of (1) to (10), wherein
[0028] In the case where the resin X has a polymerizable group, the composition further comprises a photopolymerization initiator.
[0029] When the resin X does not have a polymerizable group, the composition further contains a polymerizable compound and a photopolymerization initiator.
[0030] (12) The composition according to any one of (1) to (10), further comprising a polymerizable compound.
[0031] (13) The composition according to (12), wherein the content of the polymerizable compound is 25.0% by mass or less based on the total solid content of the composition.
[0032] (14) The composition according to any one of (1) to (13), further comprising a compound Y having no ethylenically polymerizable group and having a boiling point of 300° C. or higher.
[0033] (15) The composition according to (14), further comprising a polymerizable compound and a compound Y,
[0034] The total content of the polymerizable compound and the compound Y is 30.0% by mass or less based on the total solid content of the composition.
[0035] (16) The composition according to any one of (11) to (15), further comprising a photopolymerization initiator, wherein the content of the photopolymerization initiator is 5.0% by mass or less based on the total solid content of the composition.
[0036] (17) The composition according to any one of (1) to (16), wherein
[0037] The composition further contains no sodium ions, or,
[0038] When the composition contains sodium ions, the content of the sodium ions is less than 50 ppm by mass based on the total solid content of the composition.
[0039] (18) The composition according to any one of (1) to (17), wherein
[0040] Furthermore, no chloride ions are contained, or, when chloride ions are contained, the content of chloride ions is less than 50 mass ppm based on the total solid content of the composition.
[0041] (19) The composition according to (11), wherein the average value X of the linear expansion coefficient of a film obtained by the method A described below in the range of 50 to 100° C. is 20 ppm / K or less.
[0042] (20) A composition according to (11) or (19), wherein the ratio of the average value Y of the linear expansion coefficient of the film obtained by the method A described later in the range of 190 to 210°C to the average value X of the linear expansion coefficient of the film in the range of 50 to 100°C is less than 2.0.
[0043] (21) The composition according to any one of (11), (19) or (20), wherein the average relative dielectric constant of a film obtained by the method A described below at 28 GHz is 3.5 or less.
[0044] (22) The composition according to any one of (11) or (19) to (21), wherein the average dielectric loss tangent of a film obtained by the method A described below at 28 GHz is 0.0030 or less.
[0045] (23) The composition according to any one of (1) to (10), further comprising a photoacid generator, wherein the resin X comprises a precursor having a group that decomposes by the action of an acid to generate a polar group.
[0046] (24) The composition according to (23), wherein the content of the photoacid generator is 5.0 mass % or less based on the total solid content of the composition.
[0047] (25) The composition according to (23) or (24), wherein the average value X of the linear expansion coefficient of a film obtained by the method B described below in the range of 50 to 100°C is 20 ppm / K or less.
[0048] (26) A composition according to any one of (23) to (25), wherein the ratio of the average value Y of the linear expansion coefficient of the film in the range of 190 to 210°C to the average value X of the linear expansion coefficient of the film obtained by the method B described later in the range of 50 to 100°C is less than 2.0.
[0049] (27) The composition according to any one of (23) to (26), wherein a film obtained by the method B described below has an average relative dielectric constant of 3.5 or less at 28 GHz.
[0050] (28) The composition according to any one of (23) to (27), wherein a film obtained by the method B described below has an average dielectric loss tangent of 0.0030 or less at 28 GHz.
[0051] (29) A transfer film comprising a temporary support and a composition layer formed using the composition according to any one of (1) to (28).
[0052] (30) A method for producing a laminate, comprising the steps of: forming a composition layer on a substrate using the composition according to any one of (1) to (28) or the transfer film according to (29);
[0053] exposing the composition layer to pattern exposure; and
[0054] The exposed composition layer is developed using a developer to form a pattern,
[0055] The developer includes at least one selected from cyclopentanone, tetramethylammonium hydroxide aqueous solution, sodium hydroxide aqueous solution, sodium carbonate aqueous solution and potassium carbonate aqueous solution.
[0056] (31) A laminated body produced by the method for producing a laminated body described in (30).
[0057] (32) A method for manufacturing a semiconductor package, comprising the method for manufacturing a laminated body according to (30).
[0058] Effects of the Invention
[0059] According to the present invention, a composition capable of forming a film having excellent cyclic thermal characteristics can be provided.
[0060] Furthermore, a transfer film, a method for producing a laminate, a laminate, and a method for producing a semiconductor package related to the composition can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 It is a diagram (nomogram) for explaining the method of measuring the boiling point of compound Y.
[0062] Figure 2 This is a schematic diagram showing an example of the layer structure of the transfer film. DETAILED DESCRIPTION
[0063] Hereinafter, the present invention will be described in detail.
[0064] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0065] Furthermore, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced by the upper limit or lower limit of another numerical range described in another stage. Furthermore, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced by the value shown in the embodiments.
[0066] Furthermore, the term "process" in this specification includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0067] In this specification, unless otherwise specified, the temperature condition may be set to 25° C. For example, the temperature when performing each of the above steps may be 25° C. unless otherwise specified.
[0068] In the present specification, "transparent" means that the average transmittance of visible light with a wavelength of 400 to 700 nm is 80% or more, preferably 90% or more.
[0069] The average transmittance of visible light is a value measured using a spectrophotometer, and can be measured using, for example, a spectrophotometer U-3310 manufactured by Hitachi, Ltd.
[0070] In this specification, "activating light" or "radiation" refers to, for example, the bright line spectrum of mercury lamps such as g-rays, h-rays and i-rays, far ultraviolet rays represented by excimer lasers, extreme ultraviolet rays (EUV rays), X-rays and electron beams (EB). In addition, in the present invention, light refers to activating light or radiation.
[0071] In this specification, unless otherwise specified, "exposure" includes not only exposure using a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light, X-rays and EUV light, but also drawing using particle beams such as electron beams and ion beams.
[0072] In this specification, unless otherwise specified, the content ratio of each repeating unit of a polymer is a molar ratio.
[0073] In addition, in this specification, unless otherwise specified, the refractive index is a value measured by an ellipsometer at a wavelength of 550 nm.
[0074] In this specification, unless otherwise specified, the molecular weight when there is a molecular weight distribution is the weight average molecular weight (Mw). In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are values obtained by polystyrene conversion based on gel permeation chromatography (GPC).
[0075] In this specification, “(meth)acrylic acid” is a concept including both acrylic acid and methacrylic acid, “(meth)acryloyl” is a concept including both acryloyl and methacryloyl, and “(meth)acrylate” is a concept including both acrylate and methacrylate.
[0076] In this specification, "water-soluble" means that the solubility in 100 g of water at a pH of 7.0 at a liquid temperature of 22°C is 0.1 g or more.
[0077] The "solid content" of a composition refers to the components that form a composition layer formed using the composition, and when the composition contains a solvent (e.g., an organic solvent and water, etc.), it refers to all components other than the solvent. In addition, if it is a component that forms a composition layer, a liquid component is also considered a solid component.
[0078] In this specification, unless otherwise specified, the thickness of a layer (film thickness) is as follows: the thickness of 0.5 μm or more is the average thickness measured using a scanning electron microscope (SEM), and the thickness of less than 0.5 μm is the average thickness measured using a transmission electron microscope (TEM). The above average thickness is the average thickness obtained by making a slice of the measurement object using an ultramicrotome, measuring the thickness of any five points, and arithmetically averaging them.
[0079] [Composition]
[0080] The composition of the present invention comprises a resin X and a filler, wherein the resin X comprises at least one selected from polyimide, polybenzoxazole and their precursors (including at least one selected from polyimide precursor, polyimide, polybenzoxazole precursor and polybenzoxazole), wherein the content of the filler is 50.0% by mass or more relative to the total solid content of the composition, and the average particle size of the filler is 300 nm or less.
[0081] The detailed mechanism of action of the composition of the present invention is not clear, but the present inventors speculate as follows: It is speculated that a film formed using the composition of the present invention contains the resin X and a predetermined amount or more of a predetermined filler, and thus a film having excellent cyclic thermal characteristics can be obtained.
[0082] Furthermore, the film formed as described above may be in a pattern.
[0083] Hereinafter, the fact that the cyclic thermal characteristics of the formed film are more excellent is also referred to as “the effect of the present invention is more excellent”.
[0084] An example of an embodiment of the composition is shown below.
[0085] Implementation method X1:
[0086] A composition comprising a resin X, a filler and a thermal alkali generator,
[0087] The resin X includes at least one selected from a polyimide precursor and a polybenzoxazole precursor.
[0088] Implementation method Y1:
[0089] A composition comprising a resin X and a filler,
[0090] When the resin X has a polymerizable group, a photopolymerization initiator is further included.
[0091] When the resin X does not have a polymerizable group, it further includes a polymerizable compound and a photopolymerization initiator.
[0092] Implementation method Y2:
[0093] A composition comprising a resin X, a filler, a polymerizable compound, a photopolymerization initiator and a thermal base generator,
[0094] The resin X includes at least one selected from a polyimide precursor and a polybenzoxazole precursor.
[0095] Implementation method Y3:
[0096] A composition comprising a resin X, a filler, a polymerizable compound, a photopolymerization initiator and a thermal base generator,
[0097] The resin X comprises at least one selected from a polyimide precursor and a polybenzoxazole precursor, and
[0098] Contains substantially no photoacid generator.
[0099] Implementation method Z1:
[0100] A composition comprising a resin X, a filler and a photoacid generator,
[0101] The resin X comprises at least one selected from a polyimide precursor and a polybenzoxazole precursor.
[0102] The above-mentioned precursor has a group which is decomposed by the action of an acid to generate a polar group.
[0103] Implementation method Z2:
[0104] A composition comprising a resin X, a filler, a photoacid generator and a thermal base generator,
[0105] The resin X comprises at least one selected from a polyimide precursor and a polybenzoxazole precursor.
[0106] The above precursor has a group that decomposes by the action of an acid to generate a polar group,
[0107] It contains substantially no photopolymerization initiator.
[0108] In the above-mentioned embodiment Y1, when the resin X has a polymerizable group, the composition may further contain a polymerizable compound.
[0109] Furthermore, in the above-mentioned embodiment Y2, the resin X may or may not have a polymerizable group.
[0110] When the composition in the method for producing a laminate described below is in Embodiments Y1 to Y3, it is preferred that the exposed portion forms a pattern (film). The composition is preferably a so-called negative resist.
[0111] When the composition in the method for producing a laminate described below is in the embodiment Z1 or Z2, it is preferable that the unexposed portion forms a pattern (film). The composition is preferably a so-called positive resist.
[0112] In the above embodiment, “substantially no photoacid generator is contained” means that the content of the photoacid generator may be less than 0.1% by mass, preferably 0 to 0.05% by mass, and more preferably 0 to 0.01% by mass, based on the total solid content of the composition.
[0113] Furthermore, “substantially containing no photopolymerization initiator” means that the content of the photopolymerization initiator may be less than 0.1% by mass, preferably 0 to 0.05% by mass, and more preferably 0 to 0.01% by mass, based on the total solid content of the composition.
[0114] Hereinafter, various components that may be contained in the composition of the present invention will be described in detail.
[0115] 〔Resin X〕
[0116] The composition includes a resin X.
[0117] The resin X is a resin containing at least one selected from polyimide, polybenzoxazole, and precursor compositions thereof. In other words, the resin X contains at least one selected from a polyimide precursor, a polyimide, a polybenzoxazole precursor, and polybenzoxazole.
[0118] Furthermore, the resin X is a compound different from various components (for example, polymerizable compounds, etc.) described later.
[0119] In addition, the polyimide precursor refers to a resin that is converted into polyimide by heat treatment or chemical treatment. In addition, the polybenzoxazole precursor refers to a resin that is converted into polybenzoxazole by heat treatment or chemical treatment.
[0120] The resin X may have a polymerizable group.
[0121] Examples of the polymerizable group include known polymerizable groups such as a radical polymerizable group, an epoxy group, an oxetanyl group, a hydroxymethyl group, and an alkoxymethyl group.
[0122] As the radical polymerizable group, a group having an ethylenically unsaturated bond is preferred.
[0123] Examples of the group having an ethylenically unsaturated bond include a (meth)acrylamide group and a (meth)acryloyl group, and a (meth)acryloyl group is preferred.
[0124] The resin X preferably has a polymerizable group that can polymerize with a polymerizable group in a polymerizable compound described below.
[0125] As described in the above embodiment Y1, when the resin X has a polymerizable group, the composition preferably contains a photopolymerization initiator.
[0126] The resin X may have a group that is decomposed by the action of an acid to generate a polar group.
[0127] When the composition is in Embodiment Z1 or Embodiment Z2, the resin X preferably has a group that generates a polar group by the action of an acid (hereinafter also referred to as an "acid-decomposable group"), and the resin X more preferably contains a polyimide precursor having an acid-decomposable group or a polybenzoxazole precursor having an acid-decomposable group.
[0128] The acid-decomposable group preferably has a structure in which a polar group is protected by a leaving group that leaves by the action of an acid. The polarity of the resin X containing a repeating unit having an acid-decomposable group increases by the action of an acid, thereby increasing its solubility in an alkaline developer and decreasing its solubility in an organic solvent developer.
[0129] Examples of the polar group include a carboxyl group, a phenolic hydroxyl group, a fluorinated alcohol group, a sulfonic acid group, a phosphoric acid group, a sulfonamide group, and an alcoholic hydroxyl group.
[0130] The polar group is preferably a carboxyl group, a phenolic hydroxyl group, a fluorinated alcohol group (preferably a hexafluoroisopropanol group), or a sulfonic acid group, and more preferably a carboxyl group or a phenolic hydroxyl group.
[0131] Examples of the leaving group that leaves by the action of an acid include groups represented by any of the formulae (Y1) to (Y4).
[0132] Formula (Y1): -C(R x1 )(R x2 )(R x3 )
[0133] Formula (Y2): -C(=O)OC(R x1 )(R x2 )(R x3 )
[0134] Formula (Y3): -C(R 36 )(R 37 )(OR 38 )
[0135] Formula (Y4): -C(Rn)(H)(Ar)
[0136] In formula (Y1) and formula (Y2), R x1 ~R x3 Each independently represents an alkyl group (which may be straight-chain, branched or cyclic), an alkenyl group (straight-chain or branched) or an aryl group (monocyclic or polycyclic). x1~R x3 When all of R are linear or branched alkyl groups, x1 ~R x3 At least two of them are preferably methyl groups.
[0137] Among them, R x1 ~R x3 A linear or branched alkyl group is preferred, and a linear alkyl group is more preferred.
[0138] R x1 ~R x3 Two of them may be bonded to form a monocyclic or polycyclic ring.
[0139] As R x1 ~R x3 The linear or branched alkyl group is preferably an alkyl group having 1 to 5 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl and tert-butyl.
[0140] As R x1 ~R x3 The cyclic alkyl group (cycloalkyl group) is preferably a monocyclic cycloalkyl group such as cyclopentyl and cyclohexyl, or a polycyclic cycloalkyl group such as norbornyl, tetracyclodecyl, tetracyclododecyl and adamantyl.
[0141] As R x1 ~R x3 The aryl group is preferably an aryl group having 6 to 10 carbon atoms, and examples thereof include phenyl, naphthyl and anthracenyl.
[0142] As R x1 ~R x3 The alkenyl group is preferably a vinyl group.
[0143] As R x1 ~R x3 The ring formed by two bonds in is preferably a cycloalkyl group. The cycloalkyl group is preferably a monocyclic cycloalkyl group such as cyclopentyl or cyclohexyl, or a polycyclic cycloalkyl group such as norbornyl, tetracyclodecyl, tetracyclododecyl or adamantyl, and more preferably a monocyclic cycloalkyl group having 5 to 6 carbon atoms.
[0144] R x1 ~R x3 In the cycloalkyl formed by two bonds in the above, one of the methylene groups constituting the ring may be substituted by a group containing a hetero atom such as an oxygen atom, a hetero atom such as a carbonyl group, or a vinylene group. Furthermore, in these cycloalkyl groups, one or more of the vinyl groups constituting the cycloalkane ring may be substituted by a vinylene group.
[0145] The group represented by formula (Y1) or formula (Y2) is preferably, for example, R x1 is methyl or ethyl, and R x2 and Rx3 The above-mentioned cycloalkyl groups are bonded to form the above-mentioned cycloalkyl groups.
[0146] In formula (Y3), R 36 ~R 38 R each independently represents a hydrogen atom or a monovalent organic group. 37 and R 38 They may be bonded to each other to form a ring. Examples of the monovalent organic group include an alkyl group (which may be linear, branched, or cyclic), an aryl group, an aralkyl group, and an alkenyl group. 36 A hydrogen atom is also preferred.
[0147] In addition, the above-mentioned alkyl, aryl and aralkyl groups may contain groups containing heteroatoms such as oxygen atoms and / or heteroatoms such as carbonyl groups. For example, in the above-mentioned alkyl, aryl and aralkyl groups, one or more methylene groups may be substituted by groups containing heteroatoms such as oxygen atoms and / or heteroatoms such as carbonyl groups.
[0148] And, R 38 R may bond with another substituent on the main chain of the repeating unit to form a ring. 38 The group formed by mutually bonding with another substituent possessed by the main chain of the repeating unit is preferably an alkylene group such as a methylene group.
[0149] As the group represented by the formula (Y3), a group represented by the formula (Y3-1) is preferred.
[0150] [Chemical formula 1]
[0151]
[0152] In formula (Y3-1), L 1 and L 2 Each independently represents a hydrogen atom, an alkyl group (which may be linear, branched or cyclic), an aryl group or a group formed by combining these (for example, a group formed by combining an alkyl group and an aryl group).
[0153] M represents a single bond or a divalent linking group.
[0154] Q represents an alkyl group which may contain a heteroatom (which may be any of linear, branched or cyclic), an aryl group which may contain a heteroatom, an amino group, an ammonium group, a mercapto group, a cyano group, an aldehyde group, or a group formed by combining them (for example, a group formed by combining a linear or branched alkyl group and a cycloalkyl group).
[0155] For example, one of the methylene groups in the alkyl group may be substituted by a group containing a hetero atom such as an oxygen atom or a hetero atom such as a carbonyl group.
[0156] In addition, L 1 and L2 One of them is preferably a hydrogen atom, and the other is an alkyl group, an aryl group, or a group composed of an alkylene group and an aryl group.
[0157] Q, M and L 1 At least two of them may be bonded to form a ring (preferably a 5-membered ring or a 6-membered ring).
[0158] As L 2 , preferably a secondary alkyl group or a tertiary alkyl group, more preferably a tertiary alkyl group. Examples of the secondary alkyl group include isopropyl, cyclohexyl and norbornyl. Examples of the tertiary alkyl group include tert-butyl and adamantyl.
[0159] L 1 and L 2 The alkyl group, aryl group and the group formed by combining them are further preferably substituted with a fluorine atom or an iodine atom. Furthermore, the alkyl group, aryl group and aralkyl group preferably contain heteroatoms such as oxygen atoms in addition to fluorine atoms and iodine atoms (i.e., in the alkyl group, aryl group and aralkyl group, for example, one of the methylene groups is substituted with a group containing heteroatoms such as oxygen atoms or heteroatoms such as carbonyl groups).
[0160] Furthermore, in the alkyl group which may contain a hetero atom represented by Q, the aryl group which may contain a hetero atom, the amino group, the ammonium group, the mercapto group, the cyano group, the aldehyde group and the group formed by combining them, the hetero atom is preferably at least one hetero atom selected from a fluorine atom, an iodine atom and an oxygen atom.
[0161] In formula (Y4), Ar represents an aromatic ring group. Rn represents an alkyl group or an aryl group. Rn and Ar may be bonded to each other to form a non-aromatic ring. Ar is preferably an aryl group.
[0162] The aromatic ring group represented by Ar and the alkyl group and aryl group represented by Rn also preferably have a fluorine atom or an iodine atom as a substituent.
[0163] From the viewpoint of excellent acid decomposability, it is also preferred that when a non-aromatic ring in a leaving group protecting a polar group is directly bonded to a polar group (or its residue), the ring atoms in the non-aromatic ring adjacent to the ring atoms directly bonded to the polar group (or its residue) do not have a halogen atom such as a fluorine atom as a substituent.
[0164] Examples of the leaving group that leaves by the action of an acid include 2-cyclopentenyl having a substituent (e.g., an alkyl group) such as 3-methyl-2-cyclopentenyl and cyclohexyl having a substituent (e.g., an alkyl group) such as 1,1,4,4-tetramethylcyclohexyl.
[0165] <Polyimide and polyimide precursor>
[0166] Polyimide is a resin having an imide structure.
[0167] The polyimide is preferably a resin having a cyclic imide structure, and may have a substituent. The polyimide is preferably a resin synthesized from a polyimide precursor having a repeating unit represented by the formula (1) described below (for example, a resin obtained by a ring closure reaction).
[0168] The polyimide precursor preferably has a repeating unit represented by formula (1).
[0169] [Chemical formula 2]
[0170]
[0171] In formula (1), A 1 and A 2 R each independently represents an oxygen atom or -NH-. 111 represents a divalent organic group. 113 and R 114 R each independently represents a hydrogen atom or a monovalent organic group. 115 It represents a tetravalent organic group.
[0172] In formula (1), A 1 and A 2 Each independently represents an oxygen atom or -NH-.
[0173] As A 1 and A 2 , preferably an oxygen atom.
[0174] In formula (1), R 111 It represents a divalent organic group.
[0175] As the above-mentioned divalent organic group, for example, a divalent aliphatic group, a divalent aromatic ring group, and a divalent group composed of a combination thereof can be cited. As the above-mentioned divalent organic group, a divalent aliphatic group having 2 to 20 carbon atoms, a divalent aromatic ring group having 6 to 20 carbon atoms, or a divalent group composed of a combination thereof is preferred, and a divalent aromatic ring group having 6 to 20 carbon atoms is more preferred. The above-mentioned divalent aliphatic group may be any of a straight chain, a branched chain, and a ring. The above-mentioned divalent aromatic ring group may be any of a monocyclic ring and a polycyclic ring. The above-mentioned divalent aliphatic group and the above-mentioned divalent aromatic ring group may have heteroatoms. The heteroatoms may be included in the divalent organic group as groups such as -O-, -CO-, -S-, -SO2-, and -NHCO-.
[0176] As R 111, and a divalent organic group derived from a diamine is also preferred. As the diamine, a diamine for producing a polyimide precursor is preferred, and an aliphatic diamine or an aromatic diamine is more preferred.
[0177] As the diamine, a diamine having a linear aliphatic group having 2 to 20 carbon atoms, a branched aliphatic group having 3 to 20 carbon atoms, a cyclic aliphatic group having 3 to 20 carbon atoms, an aromatic ring group having 6 to 20 carbon atoms, or a group composed of these is preferred, and a diamine having an aromatic ring group having 6 to 20 carbon atoms (aromatic diamine) is more preferred. Examples of the aromatic ring group include groups having the following structures.
[0178] [Chemical formula 3]
[0179]
[0180] In the above formula, A represents a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms which may have a fluorine atom, -O-, -CO-, -S-, -SO2-, -NHCO-, or a group formed by combining them, or a single bond. As A, at least one selected from the group consisting of an alkylene group having 1 to 3 carbon atoms which may have a fluorine atom, -O-, -CO-, -S-, and -SO2- is preferred, at least one selected from the group consisting of -CH2-, -O-, -S-, -SO2-, -C(CF3)2-, and -C(CH3)2- is more preferred, and -O- is further preferred.
[0181] R 111 Also preferably *-Ar 0 -L 0 -Ar 0 -*.
[0182] Ar 0 represents an aromatic hydrocarbon group. 0 represents an aliphatic hydrocarbon group having 1 to 10 carbon atoms which may have a fluorine atom, -O-, -CO-, -S-, -SO2-, -NHCO-, or a group formed by combining these, or a single bond. * represents a bonding position.
[0183] Ar 0 They may be the same as or different from each other.
[0184] Ar 0 The number of carbon atoms of the aromatic hydrocarbon group represented is preferably 6 to 22, more preferably 6 to 18, and further preferably 6 to 10. The aromatic hydrocarbon group is preferably a phenyl group.
[0185] L 0 The meaning and preferred aspects are the same as those of A in the above AR-8.
[0186] Specific examples of the diamine include 1,2-diaminoethane, 1,2-diaminopropane, 1,3-diaminopropane, 1,4-diaminobutane, and 1,6-diaminohexane; 1,2-diaminocyclopentane or 1,3-diaminocyclopentane, 1,2-diaminocyclohexane, 1,3-diaminocyclohexane or 1,4-diaminoaminocyclohexane, 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane or 1,4-bis(aminomethyl)cyclohexane, bis-(4-aminocyclohexyl)methane, bis-(3-aminocyclohexyl)methane, 4,4'-diamino-3,3'-dimethylcyclohexylmethane or isophoronediamine; m-phenylenediamine or p-phenylenediamine, diaminotoluene, 4,4'-diamino 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane or 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone or 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfide or 3,3'-diaminodiphenyl sulfide, 4,4'-diaminobenzophenone or 3,3'-diaminobenzophenone, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (4,4'-diamino-2,2'-dimethylbiphenyl), 3,3'-dimethoxy-4,4'-diaminobiphenyl, 2,2-bis(4-aminophenyl)propane, 2,2-bis( 4-aminophenyl)hexafluoropropane, 2,2-bis(3-hydroxy-4-aminophenyl)propane, 2,2-bis(3-hydroxy-4-aminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(4-amino-3-hydroxyphenyl)sulfone, 4,4'-diaminoterphenyl, 4,4'-bis(4-phenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(2-aminophenoxy)phenyl]sulfone, 1,4-bis(4-aminophenoxy)benzene, 9,10-bis(4-aminophenyl)anthracene, 3, 3'-Dimethyl-4,4'-diaminodiphenyl sulfone, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenyl)benzene, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminooctafluorobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 9,9-bis(4-aminophenyl)-10-hydroanthracene, 3,3',4,4'-tetraaminobiphenyl, 3,3',4,4'-tetraaminodiphenyl ether, 1,4-diaminoanthraquinone, 1,5-diaminoanthraquinone, 3,3-dihydroxy-4,4'-diaminobiphenyl, 9,9'-bis(4-aminophenyl)fluorene, 4,4'-dimethyl-3,3'-diaminodiphenyl sulfone, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 2-(3',5'-diaminobenzoyloxy)ethyl methacrylate, 2,4-diaminocumene or 2,5-diaminocumene, 2,5-dimethyl-p-phenylenediamine, acetoguanamine, 2,3,5,6-tetramethyl-p-phenylenediamine, 2,4,6-trimethyl- m-phenylenediamine, bis(3-aminopropyl)tetramethyldisiloxane, 2,7-diaminofluorene, 2,5-diaminopyridine, 1,2-bis(4-aminophenyl)ethane, diaminobenzanilide, esters of diaminobenzoic acid, 1,5-diaminonaphthalene, diaminotrifluorotoluene, 1,3-bis(4-aminophenyl)hexafluoropropane, 1,4-bis(4-aminophenyl)octafluorobutane, 1,5-bis(4-aminophenyl)decafluoropentane, 1,7-bis(4-aminophenyl)tetradecafluoroheptane, 2,2-bis[4-(3 2,2-bis[4-(2-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)-3,5-bis(trifluoromethyl)phenyl]hexafluoropropane, p-bis(4-amino-2-trifluoromethylphenoxy)benzene, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 4,4'-bis(4-amino-3-trifluoromethylphenyl) oxy) biphenyl, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)diphenyl sulfone, 4,4'-bis(3-amino-5-trifluoromethylphenoxy)diphenyl sulfone, 2,2-bis[4-(4-amino-3-trifluoromethylphenoxy)phenyl]hexafluoropropane, 3,3',5,5'-tetramethyl-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,2',5,5',6,6'-hexafluorotoluidine and 4,4'-diaminoquatphenyl.
[0187] Furthermore, examples of the diamine include compounds represented by any one of Formula (DA-1) to Formula (DA-18).
[0188] [Chemical formula 4]
[0189]
[0190] [Chemical formula 5]
[0191]
[0192] Furthermore, as the diamine, there can be mentioned a diamine having two or more alkylene glycol units in the main chain, and as the diamine having the above two or more alkylene glycol units in the main chain, a diamine containing two or more ethylene glycol chains and one or two propylene glycol chains in total in one molecule is preferred. Furthermore, a diamine not containing an aromatic ring is also preferred.
[0193] Examples of the diamine include JEFFAMINE (registered trademark) series (KH-511, ED-600, ED-900, ED-2003, EDR-148, EDR-176, D-200, D-400, D-2000, and D-4000, manufactured by HUNTSMAN), 1-(2-(2-(2-aminopropoxy)ethoxy)propoxy)propan-2-amine, and 1-(1-(1-(2-aminopropoxy)propan-2-yl)oxy)propan-2-amine.
[0194] R 113 and R 114 Each independently represents a hydrogen atom or a monovalent organic group.
[0195] R 113 and R 114 At least one of them preferably represents a group having a polymerizable group, and more preferably R 113 and R 114 These two represent groups having a polymerizable group. Examples of the polymerizable group include the groups exemplified in the polymerizable group that the above-mentioned resin X may have.
[0196] The monovalent organic group may be a monovalent organic group X described below.
[0197] As R 113 and R 114 , preferably a group having an ethylenically unsaturated group, more preferably a vinyl group, an allyl group, a (meth)acryloyl group or a group represented by formula (III).
[0198] [Chemical formula 6]
[0199]
[0200] In formula (III), R 200 represents a hydrogen atom or a methyl group. 201 It represents an alkylene group having 2 to 12 carbon atoms, -CH2CH(OH)CH2-, or a (poly)oxyalkylene group having 4 to 30 carbon atoms. * represents a bonding position.
[0201] In formula (III), R 200 represents a hydrogen atom or a methyl group.
[0202] As R200 , preferably methyl.
[0203] In formula (III), R 201 It represents an alkylene group having 2 to 12 carbon atoms, -CH2CH(OH)CH2-, or a (poly)oxyalkylene group having 4 to 30 carbon atoms.
[0204] The carbon number of the alkylene group constituting the (poly)oxyalkylene group is preferably 1-12, more preferably 1-6, and even more preferably 1-3. The number of repetitions of the oxyalkylene group constituting the (poly)oxyalkylene group is preferably 1-12, more preferably 1-6, and even more preferably 1-3.
[0205] In addition, the (poly)oxyalkylene group is a concept including both an oxyalkylene group and a polyoxyalkylene group.
[0206] As R 201 , for example, vinyl, propylene, trimethylene, tetramethylene, 1,2-butanediyl, 1,3-butanediyl, pentamethylene, hexamethylene, octamethylene, dodecamethylene and -CH2CH(OH)CH2-, preferably vinyl, propylene, trimethylene or -CH2CH(OH)CH2-, more preferably vinyl.
[0207] As R 113 or R 114 The monovalent organic group represented by the present invention includes aliphatic groups, aromatic ring groups and aralkyl groups having 1 to 3 acid groups. For example, aromatic ring groups having 6 to 20 carbon atoms and aralkyl groups having 7 to 25 carbon atoms can be mentioned. More specifically, phenyl groups having acid groups and benzyl groups having acid groups can be mentioned. The acid groups are preferably hydroxyl groups or carboxyl groups.
[0208] As R 113 and R 114 , a hydrogen atom, a 2-hydroxybenzyl group, a 3-hydroxybenzyl group or a 4-hydroxybenzyl group is also preferred.
[0209] As R 113 or R 114 The monovalent organic group represented may include a leaving group that is released by the action of the above-mentioned acid, and may be a group represented by any of the above-mentioned formulae (Y1) to (Y4).
[0210] In formula (1), R 115 It represents a tetravalent organic group.
[0211] The tetravalent organic group is preferably a tetravalent organic group having an aromatic ring, and more preferably a group represented by the formula (5) or a group represented by the formula (6).
[0212] [Chemical formula 7]
[0213]
[0214] In formula (5), R 112 It represents a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms which may have a fluorine atom, -O-, -CO-, -S-, -SO2-, -NHCO-, or a group composed of these, or a single bond. * represents a bonding position.
[0215] In formula (6), * represents a bonding position.
[0216] In formula (5), R 112 The meaning and preferred aspects are the same as those of A in the above AR-8.
[0217] As a tetravalent organic group, a tetracarboxylic acid residue remaining after removing the acid dianhydride group from tetracarboxylic dianhydride is also mentioned, for example. Tetracarboxylic dianhydride is preferably a compound represented by formula (7).
[0218] [Chemical formula 8]
[0219]
[0220] In formula (7), R 115 It represents a tetravalent organic group.
[0221] R in formula (7) 115 With R in formula (1) 115 The meaning is the same and the preferred method is also the same.
[0222] Examples of the tetracarboxylic dianhydride include pyromellitic acid, pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfide tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenylmethane tetracarboxylic dianhydride, 2,2',3,3'-diphenylmethane tetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,4,5,7-naphthalene tetracarboxylic dianhydride, and 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride. , 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 1,3-diphenylhexafluoropropane-3,3,4,4-tetracarboxylic dianhydride, 1,4,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-diphenyltetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 1,2,4,5-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,8,9,10-phenanthrenetetracarboxylic dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, and alkyl derivatives having 1 to 6 carbon atoms and alkoxy derivatives having 1 to 6 carbon atoms thereof.
[0223] As a tetracarboxylic dianhydride, the compound represented by any one of Formula (DAA-1) - Formula (DAA-5) is mentioned, for example.
[0224] [Chemical formula 9]
[0225]
[0226] (monovalent organic group X)
[0227] As the monovalent organic group X, an alkyl group which may have a substituent or an aromatic ring group which may have a substituent is preferred, and an alkyl group which may have an aromatic ring group is more preferred.
[0228] The alkyl group may be linear, branched or cyclic, and the cyclic group may be monocyclic or polycyclic.
[0229] The number of carbon atoms in the linear or branched alkyl group is preferably 1 to 30. The number of carbon atoms in the cyclic alkyl group (cycloalkyl group) is preferably 3 to 30.
[0230] Examples of the alkyl group include linear or branched alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, octadecyl, isopropyl, isobutyl, sec-butyl, tert-butyl, 1-ethylpentyl and 2-ethylhexyl; monocyclic cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl and cyclooctyl; and polycyclic cycloalkyl groups such as adamantyl, norbornyl, bornyl, camphenyl, decahydronaphthyl, tricyclodecyl, tetracyclodecyl, camphoryl, dicyclohexyl and pinenyl.
[0231] As a substituent which the said alkyl group may have, an aromatic ring group mentioned later is preferable.
[0232] The aromatic ring group may be any of an aromatic hydrocarbon ring group and an aromatic heterocyclic group. Furthermore, the aromatic ring group may be any of a monocyclic ring and a polycyclic ring.
[0233] Examples of the ring constituting the aromatic ring group include a benzene ring, a naphthalene ring, a biphenyl ring, a fluorene ring, a pentadiene ring, an indene ring, an azulene ring, a heptadiene ring, a benzodiindene ring, a perylene ring, a pentacyclic ring, an acenaphthene ring, a phenanthrene ring, an anthracene ring, a tetracene ring, Aromatic hydrocarbon rings such as fluorene ring, pyrrole ring, furan ring, thiophene ring, imidazole ring, oxazole ring, thiazole ring, pyridine ring, pyrazine ring, pyrimidine ring, pyridazine ring, indolizine ring, indole ring, benzofuran ring, benzothiophene ring, isobenzofuran ring, quinolizine ring, quinoline ring, phthalazine ring, naphthyridine ring, quinoxaline ring, quinazoline ring, isoquinoline ring, carbazole ring, phenanthridine ring, acridine ring, phenanthroline ring, thianthrene ring, benzopyran ring, gadolinium ring, phenoxathiol ring, phenothiazine ring and phenazine ring.
[0234] As the substituent which the above-mentioned aromatic ring group may have, the above-mentioned alkyl group is preferable.
[0235] The polyimide precursor also preferably has a fluorine atom.
[0236] The content of fluorine atoms in the polyimide precursor is preferably 10% by mass or more, more preferably 20% by mass or more, relative to the total mass of the polyimide precursor. The upper limit is preferably 50% by mass or less.
[0237] From the viewpoint of improving the adhesion to the substrate, the polyimide precursor can be obtained by copolymerizing the repeating unit represented by formula (1) and an aliphatic group having a siloxane structure. Examples of the aliphatic group having a siloxane structure include bis(3-aminopropyl)tetramethyldisiloxane and bis(p-aminophenyl)octamethylpentasiloxane.
[0238] The repeating unit represented by the formula (1) is preferably a repeating unit represented by the formula (1-A) or a repeating unit represented by the formula (1-B).
[0239] [Chemical formula 10]
[0240]
[0241] A 11 and A 12 represents an oxygen atom or -NH-. 111 and R 112 R each independently represents a divalent organic group. 113 and R 114 Each independently represents a hydrogen atom or a monovalent organic group.
[0242] In formula (1-A), A 11 , A 12 , R 111 , R 113 and R 114 Respectively with A in formula (1) 1 , A 2 , R 111 , R 113 and R 114 The meanings are the same and the preferred aspects are also the same.
[0243] In formula (1-A), R 112 With R in formula (5) 112 The meaning is the same and the preferred method is also the same.
[0244] In the formula (1-A), the bonding positions of the carbonyl group to the benzene ring are preferably 4, 5, 3' and 4' in the formula (1-A).
[0245] In formula (1-B), the bonding positions of the carbonyl group to the benzene ring are preferably 1, 2, 4, and 5 in formula (1-B).
[0246] The polyimide precursor may contain other repeating units in addition to the repeating unit represented by the formula (1).
[0247] The content of the repeating unit represented by formula (1) is preferably 50 mol% or more, more preferably 70 mol% or more, and further preferably 90 mol% or more relative to all repeating units of the polyimide precursor. The upper limit is preferably 100 mol% or less.
[0248] The weight average molecular weight (Mw) of the polyimide precursor is preferably 2,000 to 500,000, more preferably 5,000 to 100,000, and further preferably 10,000 to 50,000. The number average molecular weight (Mn) of the polyimide precursor is preferably 800 to 250,000, more preferably 2,000 to 50,000, and further preferably 4,000 to 25,000.
[0249] The dispersion degree (Mw / Mn) of the polyimide precursor is preferably 1.5 to 3.5, more preferably 2.0 to 3.0.
[0250] <Polybenzoxazole and polybenzoxazole precursor>
[0251] Polybenzoxazole is a resin having a benzoxazole ring.
[0252] The polybenzoxazole is not particularly limited as long as it is a resin having a benzoxazole ring, and may have a substituent. The polybenzoxazole is preferably a resin synthesized from a polybenzoxazole precursor having a repeating unit represented by formula (2) described below (for example, a resin obtained by a ring-closing reaction).
[0253] The polybenzoxazole precursor preferably has a repeating unit represented by formula (2).
[0254] [Chemical formula 11]
[0255]
[0256] In formula (2), R 121 represents a divalent organic group. 122 represents a tetravalent organic group. 123 and R 124 Each independently represents a hydrogen atom or a monovalent organic group.
[0257] In formula (2), R 121 It represents a divalent organic group.
[0258] Examples of the divalent organic group include R 111 A divalent organic group represented by.
[0259] In formula (2), R 122 It represents a tetravalent organic group.
[0260] Examples of the tetravalent organic group include R 115 The tetravalent organic group represented by .
[0261] In formula (2), R 123 and R 124 Each independently represents a hydrogen atom or a monovalent organic group.
[0262] R 123 and R 124 With R 113 and R 114 The meaning is the same and the preferred method is also the same.
[0263] The polybenzoxazole precursor may contain other repeating units in addition to the repeating unit represented by the formula (2).
[0264] As other repeating units, for example, repeating units having a siloxane structure can be mentioned. As the above-mentioned other repeating units, for example, repeating units described in paragraphs 0150 to 0154 of JP-A-2020-154205 can be mentioned.
[0265] The weight average molecular weight (Mw) of the polybenzoxazole precursor is preferably 2,000 to 500,000, more preferably 5,000 to 100,000, and even more preferably 10,000 to 50,000.
[0266] The number average molecular weight (Mn) of the polybenzoxazole precursor is preferably 800 to 250,000, more preferably 2,000 to 50,000, and even more preferably 4,000 to 25,000.
[0267] The dispersion degree (Mw / Mn) of the polybenzoxazole precursor is preferably 1.5 to 3.5, more preferably 2.0 to 3.0.
[0268] The resin X may be used alone or in combination of two or more.
[0269] The content of the resin X is preferably 5.0% by mass or more, more preferably 10.0% by mass or more, relative to the total solid content of the composition. The upper limit is preferably 50.0% by mass or less, more preferably 30.0% by mass or less, relative to the total solid content of the composition.
[0270] 〔filler〕
[0271] The composition comprises a filler.
[0272] The content of the filler is 50.0% by mass or more, preferably 60.0% by mass or more, and more preferably 70.0% by mass or more, relative to the total solid content of the composition. The upper limit is preferably 90.0% by mass or less, and more preferably 80.0% by mass or less.
[0273] The average particle size of the filler is 300 nm or less, preferably 200 nm or less, and more preferably 100 nm or less. The lower limit is preferably more than 0 nm, and more preferably 5 nm or more. Furthermore, the average particle size of the filler is also preferably 5 to 100 nm.
[0274] The average particle size of the filler is calculated by the following particle size measurement method.
[0275] Particle size measurement method: The composition is applied on a substrate to form a coating film, and a 3μm×10μm rectangular area in a cross section along the normal direction of the surface of the coating film is observed using a scanning electron microscope. The long diameters of all fillers observed in the above-mentioned area are measured at 5 different locations on the coating film, and the average value of the long diameters of all fillers measured by each operation is taken as the average particle size of the filler.
[0276] The steps of the above-mentioned particle size measurement method are described in detail.
[0277] First, the composition is applied on a substrate to form a coating film. The thickness of the coating film is preferably 3 μm or more. As the substrate used, a glass substrate is used. When forming the coating film, a drying treatment may be performed as needed.
[0278] A cross section along the normal direction of the surface of the obtained coating film (the surface on the side opposite to the substrate side) was cut out, and a rectangular area of 3 μm×10 μm of the cross section was observed with a scanning electron microscope, and the major diameters of all fillers observed in the above area were measured. As a scanning electron microscope, S-4800 manufactured by Hitachi High-Tech Corporation was used. In addition, the magnification during observation was 50,000 times.
[0279] The above operation was performed at five different locations on the coating film, and the average value (arithmetic mean value) of the major diameters of all the fillers measured by the respective operations was taken as the average particle size of the filler.
[0280] The major axis refers to the length of the longest line segment among the line segments connecting any two points on the contour line of the filler in the observation image.
[0281] Furthermore, when fillers aggregate to form aggregates in the observed image, the major diameters of the fillers forming the aggregates are measured.
[0282] Examples of the filler include organic fillers and inorganic fillers, and inorganic fillers are preferred.
[0283] As fillers, for example, there can be mentioned silicon dioxide (Silica); silicates such as kaolinite, kaolin clay, calcined clay, talc and glass fillers such as undoped glass; aluminum oxide, barium sulfate, mica powder, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum borate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, calcium zirconate, zirconium phosphate, cordierite, zirconium tungstate and manganese nitride.
[0284] The filler preferably includes at least one selected from the group consisting of silica, boron nitride, barium sulfate and silicate, and more preferably includes silica.
[0285] The shape of the filler may be any of spherical and non-spherical (for example, crushed and fibrous), but is preferably spherical.
[0286] The filler may be surface treated. In other words, the filler is preferably surface treated with a surface modifier. As surface treatment, for example, treatment of introducing functional groups and treatment using known surface modifiers (for example, liquid phase treatment and gas phase treatment) can be cited. As the above-mentioned functional group, for example, a polymerizable group (for example, a polymerizable group possessed by a polymerizable compound described later) and a hydrophobic group can be cited.
[0287] The filler is surface-treated with a surface modifier, which means that at least a portion of the surface of the filler is covered with the surface modifier or a component derived from the surface modifier. That is, the filler is surface-treated with a surface modifier, which means that at least a portion of the surface is covered with the surface modifier or a component derived from the surface modifier. In addition, regarding the component derived from the surface modifier, when the surface modifier is a hydrolyzable compound, hydrolyzates of the surface modifier and hydrolysis-condensation products thereof can be cited.
[0288] Preferably, at least a portion of the surface of the filler is covered with the surface modifier or a component derived from the surface modifier via a chemical bond, and more preferably at least a portion of the surface of the filler is covered with the surface modifier via a "-Si-O-" bond.
[0289] Examples of the surface modifier include known surface modifiers such as silane coupling agents, titanate coupling agents, and silazane compounds.
[0290] The silane coupling agent is, for example, a compound having a hydrolyzable group directly bonded to a Si atom.
[0291] Examples of the hydrolyzable group include an alkoxy group (preferably having 1 to 10 carbon atoms) and a halogen atom such as a chlorine atom.
[0292] The number of hydrolyzable groups directly bonded to Si atoms in the silane coupling agent is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. The upper limit is preferably 10,000 or less.
[0293] The silane coupling agent also preferably has a functional group other than the hydrolyzable group.
[0294] Examples of the functional group include (meth)acryloyl, phenyl, silazane, epoxy, oxetanyl, vinyl, styryl, amino, isocyanate, mercapto, and anhydride groups. The number of functional groups possessed by the silane coupling agent may be one or more.
[0295] The surface modifier may be used alone or in combination of two or more.
[0296] The content of the surface modifier is usually 8% by mass or less relative to the total mass of the filler, preferably less than 5% by mass, more preferably less than 3% by mass, further preferably less than 2% by mass, and particularly preferably less than 1% by mass. The lower limit is preferably 0% by mass or more.
[0297] The content of the surface modifier is the total content of the surface modifier covering at least a portion of the filler surface and components derived from the surface modifier. In other words, the content of the surface modifier is a value excluding the surface modifier that does not cover the filler surface, i.e., the surface modifier that is free in the composition.
[0298] The content of the surface modifier is not particularly limited and can be measured by, for example, Method Z.
[0299] The composition is applied on a substrate so that the thickness after drying is 10 μm and dried to form a composition layer. The temperature during the drying is preferably 50 to 150° C., more preferably 70 to 100° C. The heating time during the drying is preferably 1 to 10 minutes, more preferably 2 to 7 minutes.
[0300] Next, the obtained composition layer is dissolved using a mixed solvent of methyl ethyl ketone (MEK): N-methylpyrrolidone (NMP) = 1:1 to obtain a solution. Then, the filler before drying is collected by filtering the solution using centrifugal separation and a filter, and the filler before drying is further dried to obtain a filler for measurement. The temperature during the drying is preferably 50 to 150°C, and more preferably 70 to 100°C. The heating time during the drying is preferably 1 to 120 minutes, and more preferably 5 to 30 minutes. The filter can be appropriately selected according to the average particle size of the filler.
[0301] The weight loss rate of the filler for measurement was measured three times using a TG-DTA apparatus (TG / DTA7300) manufactured by Hitachi High-Tech Science Corporation under conditions of heating from room temperature to 1000°C (10°C / min) in an air atmosphere, and the content of the surface modifier was calculated from the average value.
[0302] Examples of the filler include SEAHOSTAR KE-S30 (manufactured by Nippon Shokubai Co., Ltd., silica, solid content concentration 100 mass %), NHM-3N (manufactured by Tokuyama Corporation, silica, solid content concentration 100 mass %), YA050C-MJE (manufactured by ADMATECHS COMPANY LIMITED, silica, solid content concentration 50 mass % MEK slurry), SFP-20M (manufactured by Denka Company Limited, silica), PMA-ST (manufactured by Nissan Chemical Corporation, silica), MEK-ST-L (manufactured by Nissan Chemical Corporation, silica), MEK-AC-5140Z (manufactured by Nissan Chemical Corporation, silica), MEK-EC-2430Z (manufactured by Nissan Chemical Corporation, solid content concentration 30 mass %), barium sulfate (manufactured by Japan Solvay Co., Ltd., solid content concentration 100 mass %), NHM-5N (manufactured by Tokuyama Corporation, silica, solid content concentration 100 mass %), Y50SP-AM1 (manufactured by ADMATECHS COMPANY LIMITED, silica, solid content concentration 50 mass % MEK slurry), and Y50SZ-AM1 (manufactured by ADMATECHS COMPANY LIMITED, silica, solid content concentration 50 mass % MEK slurry).
[0303] The refractive index of the filler is preferably 0.5 to 3.0, more preferably 1.2 to 1.8.
[0304] The refractive index can be measured by the above-mentioned method.
[0305] The filler may be used alone or in combination of two or more.
[0306] 〔Polymerizable compounds〕
[0307] The composition preferably contains a polymerizable compound.
[0308] The polymerizable compound is a compound different from the above-mentioned various components.
[0309] The polymerizable compound is a compound having one or more polymerizable groups in one molecule.
[0310] Examples of the polymerizable group possessed by the polymerizable compound include a (meth)acryloyl group, a vinyl group, and a styryl group. Among them, a (meth)acryloyl group is preferred, and a methacryloyl group is more preferred.
[0311] Examples of polymerizable compounds include polymerizable compounds having one polymerizable group in one molecule (hereinafter also referred to as "monofunctional polymerizable compounds"), polymerizable compounds having two polymerizable groups in one molecule (hereinafter also referred to as "bifunctional polymerizable compounds"), and polymerizable compounds having three or more polymerizable groups in one molecule (hereinafter also referred to as "trifunctional or higher polymerizable compounds").
[0312] As the polymerizable compound, a bifunctional polymerizable compound is preferred.
[0313] Examples of the bifunctional polymerizable compound include polyethylene glycol methacrylate, tricyclodecane dimethanol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. Examples of commercially available bifunctional polymerizable compounds include diethylene glycol dimethacrylate (2G, manufactured by Shin-Nakamura Chemical Co., Ltd.), triethylene glycol dimethacrylate (3G, manufactured by Shin-Nakamura Chemical Co., Ltd.), polyethylene glycol #200 dimethacrylate (4G, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol diacrylate (A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (A-NOD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0314] Examples of trifunctional or higher-functional polymerizable compounds include dipentaerythritol (tri / tetra / penta / hexa) (meth)acrylate, pentaerythritol (tri / tetra) (meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds having a glycerol tri(meth)acrylate skeleton.
[0315] “(Tri / tetra / penta / hexa) (meth)acrylate” is a concept including tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate and hexa(meth)acrylate, and “(tri / tetra) (meth)acrylate” is a concept including tri(meth)acrylate and tetra(meth)acrylate.
[0316] Examples of commercially available polymerizable compounds include caprolactone-modified compounds of (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20, etc.: manufactured by Nippon Kayaku Co., Ltd., and A-9300-1CL, etc.: manufactured by Shin-Nakamura Chemical Co., Ltd.), alkylene oxide-modified compounds of (meth)acrylate compounds (KAYARAD RP-1040, etc.: manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300, etc.: manufactured by Shin-Nakamura Chemical Co., Ltd., and EBECRYL (registered trademark) 135, etc.: manufactured by DAICEL-ALLNEX LTD.), and ethoxylated glyceryl triacrylate (A-GLY-9E, etc.: manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0317] As the polymerizable compound, for example, urethane (meth) acrylate (preferably trifunctional or higher urethane (meth) acrylate) can also be mentioned. The number of polymerizable groups possessed by the urethane (meth) acrylate is preferably 6 or more, more preferably 8 or more. The upper limit is preferably 20 or less.
[0318] Examples of trifunctional or higher-functional urethane (meth) acrylates include 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.); UA-32P, U-15HA and UA-1100H (all manufactured by Shin-Nakamura Chemical Co., Ltd.); AH-600 (manufactured by Kyoeisha Chemical Co., Ltd.); UA-306H, UA-306T, UA-306I, UA-510H and UX-5000 (all manufactured by Nippon Kayaku Co., Ltd.).
[0319] The polymerizable compound may be used alone or in combination of two or more.
[0320] The content of the polymerizable compound is preferably 30.0% by mass or less, more preferably 25.0% by mass or less, and even more preferably 20.0% by mass or less, relative to the total solid content of the composition. The lower limit is preferably 1.0% by mass or more.
[0321] 〔Photopolymerization initiator〕
[0322] The composition may include a photopolymerization initiator.
[0323] The photopolymerization initiator is a compound different from the above-mentioned various components.
[0324] Examples of the photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator, and a photoradical polymerization initiator is preferred.
[0325] Examples of the photopolymerization initiator include oxime ester compounds (photopolymerization initiators having an oxime ester structure), aminoacetophenone compounds (photopolymerization initiators having an aminoacetophenone structure), hydroxyacetophenone compounds (photopolymerization initiators having a hydroxyacetophenone structure), acylphosphine oxide compounds (photopolymerization initiators having an acylphosphine oxide structure), and bistriphenylimidazole compounds (photopolymerization initiators having a bistriphenylimidazole structure).
[0326] As the photopolymerization initiator, an oxime ester compound or an aminoacetophenone compound is preferred, and an oxime ester compound is more preferred.
[0327] Examples of the oxime ester compound include 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(0-benzoyl oxime)] (trade name: IRGACURE OXE-01, manufactured by BASF), ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(0-acetyl oxime) (trade name: IRGACURE OXE-02, manufactured by BASF), [8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazolyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(0-acetyl oxime) (trade name: IRGACURE OXE-03, manufactured by BASF), 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methylpentanone-1-(0-acetyloxime) (trade name: IRGACURE OXE-04, manufactured by BASF and trade name: Lunar 6, manufactured by DKSH Japan KK), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(0-benzoyloxime) (trade name: TR-PBG-305, manufactured by Changzhou Tronly New Electronic Materials CO., LTD.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazole-3-yl]-, 2-(0-acetyloxime) (trade name: TR-PBG-326, manufactured by Changzhou Tronly New Electronic Materials CO., LTD.) and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(0-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Tronly New Electronic Materials CO., LTD.).
[0328] Examples of the aminoacetophenone compound include 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379EG, Omnirad series, manufactured by IGM Resins B.V.), 2-methyl-1-(4-methylthiophenyl)-2-morpholinylpropane-1-one (trade name: Omnirad 907), and APi-307 (1-(biphenyl-4-yl)-2-methyl-2-morpholinylpropane-1-one, manufactured by Shenzhen UV-ChemTech Ltd.).
[0329] Examples of the photopolymerization initiator include 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one (trade name: Omnirad 127), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad 369), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (trade name: Omnirad 1173), 1-hydroxy-cyclohexyl-phenyl ketone (trade name: Omnirad 184), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnitad TP001), and 1-hydroxy-2-methyl-1-phenyl-propane-1-one (trade name: Omnirad 1173). H) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad819).
[0330] Examples of the photopolymerization initiator include the photopolymerization initiators described in paragraphs 0031 to 0042 of JP-A-2011-095716 and paragraphs 0064 to 0081 of JP-A-2015-014783.
[0331] The photopolymerization initiator may be used alone or in combination of two or more.
[0332] The content of the photopolymerization initiator is preferably 10.0% by mass or less, more preferably 5.0% by mass or less, and even more preferably 1.0% by mass or less, relative to the total solid content of the composition. The lower limit is preferably 0.1% by mass or more.
[0333] [Thermal alkali generator]
[0334] The composition may include a thermal base generator.
[0335] When the composition contains a thermal base generator, the ring-closing reaction of the polyimide precursor and the polybenzoxazole precursor is promoted, and polyimide and polybenzoxazole are easily generated, thereby achieving excellent cyclic thermal characteristics.
[0336] As the thermal base generator, an acidic compound or an onium salt compound (a compound composed of a cation and an anion) which generates a base by heating is preferred.
[0337] As the onium salt compound, an ammonium salt compound (a compound composed of an ammonium cation and an anion), an iminium salt compound (a compound composed of an iminium cation and an anion), a sulfonium salt compound (a compound composed of a sulfonium cation and an anion), an iodonium salt compound (a compound composed of an iodonium cation and an anion) or a phosphonium salt compound (a compound composed of a phosphonium cation and an anion) is preferred, and an iminium salt compound is more preferred.
[0338] As the anion constituting the onium salt compound, a carboxylate anion, a phenolate anion, a phosphate anion or a sulfate anion is preferred, and a carboxylate anion is more preferred.
[0339] The anion constituting the ammonium salt compound preferably further has an aromatic ring.
[0340] Examples of the aromatic ring include: a1 The aromatic ring of the aromatic ring group represented by .
[0341] The temperature at which the acidic compound and the onium salt compound generate a base is preferably the heating temperature in step X4 in the method for producing a laminated body described later.
[0342] The temperature at which the thermal base generator generates a base can be determined by, for example, measuring the compound to be measured by differential scanning calorimetry by heating it to 250°C at 5°C / min in a pressure-resistant capsule, reading the peak temperature of the lowest exothermic peak, and setting the peak temperature as the base generation temperature.
[0343] The base generated by the thermal base generator is preferably a secondary amine or a tertiary amine, and more preferably a tertiary amine. The base may be linear, branched, or cyclic, and is preferably cyclic.
[0344] As the acidic compound, a compound represented by formula (A1) is preferred.
[0345] [Chemical formula 12]
[0346]
[0347] In formula (A1), A a1 represents a p-valent organic group. a1 represents a monovalent organic group. a1 represents a (m+1)-valent linking group. m represents an integer greater than or equal to 1. p represents an integer greater than or equal to 1.
[0348] In formula (A1), A a1 It represents a p-valent organic group.
[0349] Examples of the organic group include an aliphatic hydrocarbon group and an aromatic ring group, and an aromatic ring group is preferred.
[0350] Examples of the monovalent aliphatic hydrocarbon group include an alkyl group and an alkenyl group.
[0351] The alkyl group may be linear, branched or cyclic.
[0352] The alkyl group has preferably 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms, and even more preferably 1 to 10 carbon atoms.
[0353] Examples of the alkyl group include a methyl group, an ethyl group, a tert-butyl group, a dodecyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, and an adamantyl group.
[0354] The alkenyl group may be linear, branched or cyclic.
[0355] The alkenyl group has preferably 2 to 30 carbon atoms, more preferably 2 to 20 carbon atoms, and further preferably 2 to 10 carbon atoms.
[0356] Examples of the alkenyl group include a vinyl group, an allyl group, and a methallyl group.
[0357] Examples of the p-valent (when p is an integer of 2 or more) aliphatic hydrocarbon group include a group formed by removing (p-1) hydrogen atoms from the above-mentioned monovalent aliphatic hydrocarbon group.
[0358] The aliphatic hydrocarbon group may further have a substituent.
[0359] The aromatic ring group may be either monocyclic or polycyclic.
[0360] The aromatic ring group may be any of an aromatic hydrocarbon ring group and an aromatic heterocyclic group.
[0361] Examples of the aromatic ring group include a benzene ring group, a naphthyl ring group, a pentadienyl ring group, an indene ring group, an azulene ring group, a heptadiene ring group, a benzodiindene ring group, a perylene ring group, a pentacyclyl group, an acenaphthene ring group, a phenanthrene ring group, an anthracene ring group, a tetracene ring group, The ring group is preferably a triphenylene ring group, a fluorene ring group, a biphenyl ring group, a pyrrole ring group, a furan ring group, a thiophene ring group, an imidazole ring group, an oxazole ring group, a thiazole ring group, a pyridine ring group, a pyrazine ring group, a pyrimidine ring group, a pyridazine ring group, an indolizine ring group, an indole ring group, a benzofuran ring group, a benzothiophene ring group, an isobenzofuran ring group, a quinolizine ring group, a quinoline ring group, a phthalazine ring group, a naphthyridine ring group, a quinoxaline ring group, a quinazoline ring group, an isoquinoline ring group, a carbazole ring group, a phenanthridine ring group, an acridine ring group, a phenanthroline ring group, a thianthracene ring group, a benzopyran ring group, a pyridine ring group, a phenoxathiol ring group, a phenothiazine ring group and a phenazine ring group, preferably a benzene ring group.
[0362] The aromatic ring group may further have a substituent.
[0363] In formula (A1), R a1 It represents a monovalent organic group.
[0364] Examples of the monovalent organic group include A a1 The monovalent aliphatic hydrocarbon group and the monovalent aromatic ring group represented by are:
[0365] The monovalent organic group may further have a substituent. The substituent is preferably a carboxyl group.
[0366] In formula (A1), L a1 It represents a (m+1)-valent linking group.
[0367] Examples of the (m+1)-valent linking group include an ether group (-O-), a carbonyl group (-CO-), an ester group (-COO-), a sulfide group (-S-), -SO2-, -NR N -(R N represents a hydrogen atom or a substituent. ), a divalent linking group such as an alkylene group (preferably having 1 to 10 carbon atoms) and an alkenylene group (preferably having 2 to 10 carbon atoms); a trivalent linking group having a group represented by "-N<" and a trivalent linking group having a group represented by "-CR<" (R represents a hydrogen atom or a substituent.); a tetravalent linking group having a group represented by ">C<"; a k-valent linking group having a cyclic group such as an aromatic ring group and an alicyclic group; and a group composed of a combination of these.
[0368] In formula (A1), m represents an integer of 1 or more.
[0369] m is preferably 1 or 2, and more preferably 1.
[0370] In formula (A1), p represents an integer of 1 or more.
[0371] p is preferably 1 or 2, and more preferably 1.
[0372] As the ammonium cation constituting the ammonium salt compound, a cation represented by the formula (101) is preferred.
[0373] As the iminium cation constituting the iminium salt compound, a cation represented by the formula (102) is preferred.
[0374] [Chemical formula 13]
[0375]
[0376] In formula (101), R 1 ~R 4 R each independently represents a hydrogen atom or an aliphatic group. 1 ~R 4 At least two of them may be bonded to each other to form a ring.
[0377] In formula (102), R 5 and R 6 R each independently represents a hydrogen atom or an aliphatic group. 7 Represents an aliphatic group. 5 ~R 7 At least two of them may be bonded to each other to form a ring.
[0378] R 1 ~R4 and R 5 ~R 7 The aliphatic group represented may be any of linear, branched, and cyclic.
[0379] The aliphatic group preferably has 1 to 10 carbon atoms.
[0380] The aliphatic group is preferably an alkyl group or an alkenyl group, and more preferably an alkyl group.
[0381] The above-mentioned aliphatic group may have a substituent, and examples of the substituent include an arylcarbonyl group.
[0382] Furthermore, the methylene group (-CH2-) in the above-mentioned aliphatic group may be substituted by a heteroatom (for example, an oxygen atom, a sulfur atom, and -NR-, etc.; R represents a hydrogen atom or a substituent).
[0383] R 5 ~R 7 At least one of them is preferably an aliphatic group having -NR-, more preferably an alkyl group having -NR-.
[0384] R 5 ~R 7 At least two of them may be bonded to each other to form a ring, preferably R 5 With R 7 and R 6 With R 7 In other words, the ring formed is preferably a polycyclic heterocycle, more preferably a bicyclic heterocycle.
[0385] Examples of the thermal base generator include the thermal base generators described in International Publication No. 2018 / 038002.
[0386] The thermal base generating agent may be used alone or in combination of two or more.
[0387] The content of the thermal base generator is preferably 10.0% by mass or less, more preferably 5.0% by mass or less, and further preferably 1.0% by mass or less, relative to the total solid content of the composition. The lower limit is preferably more than 0% by mass, and more preferably 0.1% by mass or more.
[0388] The mass ratio of the content of the thermal base generator to the content of the resin X (content of the thermal base generator / content of the resin X) is preferably 1.00 or less, more preferably 0.10 or less, and further preferably 0.05 or less. The lower limit is preferably greater than 0.
[0389] [Compound Y]
[0390] The composition may also comprise compound Y.
[0391] The compound Y is a compound having no ethylenic polymerizable group and having a boiling point of 300° C. or higher.
[0392] The compound Y is a compound different from both the above-mentioned photopolymerization initiator and the above-mentioned thermal base generator.
[0393] In the case where the composition contains compound Y, when a transfer film having a composition layer formed using the composition is bonded (laminated) to a bonded object and a pattern is formed by exposure treatment, development treatment and heat treatment after development, compound Y acts as a component for ensuring the plasticity of resins such as resin X in the photosensitive layer, is volatilized and removed by heat treatment after development, and is likely to remain in the system of the pattern.
[0394] The boiling point of compound Y is 300° C. or higher, preferably 350° C. or higher. The upper limit is preferably 500° C. or lower, more preferably 480° C. or lower, and further preferably 450° C. or lower.
[0395] In this specification, the boiling point of the compound Y is set to a value determined by the following measurement method.
[0396] When compound Y was distilled under normal pressure (760 mmHg), the gas temperature at the time when the evaporated gas condensed was defined as the boiling point (measured at 23° C. to 300° C., with a temperature increase rate of 1° C. / min).
[0397] The distillation of compound Y was carried out using a Liebig condenser. Under normal pressure, if distillation did not start at 300°C, distillation was carried out under reduced pressure. The same distillation was carried out in the order of 100 mmHg, 50 mmHg and 5 mmHg (measurement was carried out at 23°C to 300°C, the temperature increase rate was 1°C / min, and if distillation did not start at 300°C, distillation was carried out at the next pressure). The temperature / pressure at which the condensation of the evaporated gas started was used. Figure 1 The boiling point at normal pressure obtained by using the nomogram shown in the literature (source: Science of Petroleum, Vol. II. p. 1281 (1938)) is set as the boiling point (calculated value). If distillation does not start at 300°C under 5 mmHg, the boiling point at normal pressure is considered to be greater than 500°C. In addition, the method of using the nomogram is as known. Specifically, the reduced pressure boiling point of the A ray and the reduced pressure degree of the C ray are connected by a straight line (step 1), and the value of the intersection of the straight line drawn in step 1 and the B ray is read (step 2), which is regarded as the boiling point at normal pressure.
[0398] The molecular weight of compound Y is preferably 200 or more, more preferably 250 or more, and even more preferably 300 or more. The upper limit is preferably 1000 or less, more preferably 800 or less, and even more preferably 600 or less.
[0399] In addition, when compound Y has a molecular weight distribution, the above molecular weight of compound Y means a weight average molecular weight.
[0400] The viscosity of compound Y at 25°C is preferably 500 mPa·s or less, more preferably 300 mPa·s or less, and further preferably 100 mPa·s or less. The lower limit is preferably 0.01 mPa·s or more, more preferably 0.05 mPa·s or more, and further preferably 0.1 mPa·s or more.
[0401] The viscosity can be measured by a B-type viscometer.
[0402] Examples of compound Y include ethylene ethyl phthalate, dihexyl phthalate, tributyl o-acetyl citrate, benzyl 2-ethylhexyl phthalate, benzyl benzoate, hexaethylene glycol monomethyl ether, pentaethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, heptaethylene glycol monomethyl ether, octaethylene glycol monomethyl ether, nonaethylene glycol monomethyl ether, pentaethylene glycol dimethyl ether, hexaethylene glycol dimethyl ether, heptaethylene glycol dimethyl ether, octaethylene glycol dimethyl ether, nonaethylene glycol dimethyl ether, bis(2-ethylhexyl) isophthalate, tripentyl phosphate, tris(2-butoxyethyl) phosphate, triethylene glycol bis-2-ethylhexanoate, tris(2-ethylhexyl) trimellitate, and bis(2-butoxyethyl) adipate.
[0403] The compound Y may be used alone or in combination of two or more.
[0404] The content of compound Y is preferably 1.0% by mass or more, more preferably 3.0% by mass or more, and further preferably 5.0% by mass or more relative to the total solid content of the composition. The upper limit is preferably 60.0% by mass or less, more preferably 50.0% by mass or less, further preferably 35.0% by mass or less, and particularly preferably 25.0% by mass or less.
[0405] The total content of the polymerizable compound and the compound Y is preferably 50.0% by mass or less, more preferably 30.0% by mass or less, and even more preferably 25.0% by mass or less, based on the total solid content of the composition.
[0406] 〔Photoacid generator〕
[0407] The composition may include a photoacid generator.
[0408] The photoacid generator is a compound that generates an acid by light (eg, exposure light, etc.).
[0409] Examples of the photoacid generator include an ionic photoacid generator and a nonionic photoacid generator.
[0410] Examples of the ionic photoacid generator include compounds having a sulfonium structure, onium salt compounds having a diaryliodonium or triarylsulfonium structure, and ammonium salt compounds having a quaternary ammonium structure. Examples of the ionic photoacid generator include those described in paragraphs 0114 to 0133 of JP-A-2014-085643.
[0411] As nonionic photoacid generators, for example, trichloromethyl-s-triazine and its derivatives (trichloromethyl-s-triazine which may have a substituent), compounds having a diazomethane structure, compounds having an imidosulfonate structure, and compounds having an oximesulfonate structure can be cited. As trichloromethyl-s-triazine and its derivatives, diazomethane compounds, and imidosulfonate compounds, for example, the compounds described in paragraphs 0083 to 0088 of Japanese Patent Publication No. 2011-221494 can be cited. And, as oximesulfonate compounds, for example, the compounds described in paragraphs 0084 to 0088 of International Publication No. 2018 / 179640 can be cited.
[0412] The photoacid generator may be used alone or in combination of two or more.
[0413] The content of the photoacid generator is preferably 0.1 to 10.0% by mass, more preferably 0.5 to 5.0% by mass, based on the total solid content of the composition.
[0414] 〔Surfactant〕
[0415] The composition may comprise a surfactant.
[0416] Examples of the surfactant include surfactants described in paragraph 0017 of Japanese Patent No. 04502784 and paragraphs 0060 to 0071 of Japanese Patent Application Laid-Open No. 2009-237362.
[0417] As the surfactant, for example, hydrocarbon surfactants, fluorine surfactants and silicone surfactants can be cited. From the viewpoint of improving environmental suitability, the surfactant preferably does not contain fluorine atoms. As the surfactant, hydrocarbon surfactants or silicone surfactants are preferred.
[0418] Examples of commercially available fluorine-based surfactants include Megafac F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-560, F-561, F-565, F-563, F-568, F-575, and F-780 (all of which are DIC CORPORATION); EXP.MFS-324, EXP.MFS-330, EXP.MFS-578, EXP.MFS-578-2, EXP.MFS-579, EXP.MFS-586, EXP.MFS-587, EXP.MFS-628, EXP.MFS-631, EXP.MFS-603, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, IF-1956, RS-90, R-94, RS-72-K and DS-21 (all made by DIC CORPORATION); Fluorad FC430, FC431 and FC171 (all made by Sumitomo 3M Limited); Surflon S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393 and KH-40 (all manufactured by AGC Inc.); PolyFox PF636, PF656, PF6320, PF6520 and PF7002 (all manufactured by OMNOVA Solutions Inc.); Ftergent 710FL, 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, 681 and 683 (all manufactured by Neos Corporation); U-120E (manufactured by Uni-chemical Co., Ltd.).
[0419] As the fluorine-based surfactant, there can be mentioned an acrylic compound having a molecular structure containing a functional group having a fluorine atom, and when heated, a portion of the functional group having a fluorine atom is cut off and the fluorine atom is volatilized. As such a fluorine-based surfactant, for example, Megafac DS series (manufactured by DIC Corporation, Chemical Industry Daily (February 22, 2016), Nikkei Industry News (February 23, 2016) and Megafac DS-21, etc.) can be mentioned.
[0420] Furthermore, the fluorine-based surfactant may be a polymer of a fluorine-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound. The fluorine-based surfactant may be a block polymer.
[0421] The fluorine-based surfactant may be a fluorine-containing polymer compound comprising a repeating unit derived from a (meth)acrylate compound having a fluorine atom and a repeating unit derived from a (meth)acrylate compound having two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy or propyleneoxy groups).
[0422] Furthermore, as the fluorine-based surfactant, for example, a fluorine-containing polymer having a group having an ethylenically unsaturated group in a side chain can also be cited. Specifically, Megafac RS-101, RS-102, RS-718K and RS-72-K (all manufactured by DIC Corporation) can be cited.
[0423] As the fluorine-based surfactant, from the viewpoint of improving environmental suitability, a surfactant derived from an alternative material to a compound having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctane acid (PFOA) and perfluorooctane sulfonic acid (PFOS), is preferred.
[0424] Examples of hydrocarbon surfactants include glycerol, trimethylolpropane, trimethylolethane, and ethoxylates and propoxylates thereof (e.g., propoxyglycerol and ethoxyglycerol, etc.); polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, and sorbitan fatty acid esters.
[0425] Examples of hydrocarbon surfactants include Pluronic (registered trademark) L10, L31, L61, L62, 10R5, 17R2 and 25R2, Tetronic 304, 701, 704, 901, 904 and 150R1, and HYDROPALAT WE 3323 (all manufactured by BASF); Solsperse 20000 (manufactured by Lubrizol Japan Limited); NCW-101, NCW-1001 and NCW-1002 (all manufactured by FUJIFILM Wako Pure Chemical Corporation); PIONIN D-1105, D-6112, D-6112-W and D-6315 (all manufactured by TAKEMOTO OIL & FAT Co., Ltd.); Olfin E1010, Surfynol 104, 400 and 440 (all manufactured by Nissin Chemical Industry Co., Ltd.).
[0426] As silicone surfactants, for example, there can be mentioned a polymer including a linear polymer composed of a siloxane bond and a modified siloxane polymer having an organic group introduced into the side chain and / or the terminal, a repeating unit having a hydrophilic group on the side chain and a repeating unit having a group having a siloxane bond on the side chain. As silicone surfactants, preferably, there are polymers including a repeating unit having a hydrophilic group on the side chain and a repeating unit having a group having a siloxane bond on the side chain. The above polymer can be any of a random copolymer and a block copolymer.
[0427] The repeating unit having a group having a siloxane bond in a side chain is preferably a repeating unit represented by formula (SX1) or a repeating unit represented by formula (SX2).
[0428] [Chemical formula 14]
[0429]
[0430] In formula (SX1), R each independently represents an alkyl group having 1 to 3 carbon atoms. 1 represents a hydrogen atom or a methyl group. 1 It represents a single bond or a divalent organic group.
[0431] When a plurality of Rs are present, Rs may be the same as or different from each other.
[0432] [Chemical formula 15]
[0433]
[0434] In formula (SX2), R 1 represents a hydrogen atom or a methyl group. 2 represents an alkylene group having 1 to 10 carbon atoms. 3 represents an alkyl group having 1 to 4 carbon atoms. n represents an integer of 5 to 50.
[0435] The repeating unit having a hydrophilic group in a side chain is preferably a repeating unit represented by the formula (SX3).
[0436] [Chemical formula 16]
[0437]
[0438] In formula (SX3), R 4 and R 5 Each independently represents a hydrogen atom or a methyl group. n represents an integer of 1 to 4. m represents an integer of 1 to 100.
[0439] Examples of the silicone surfactant include EXP.S-309-2, EXP.S-315, EXP.S-503-2, and EXP.S-505-2 (all manufactured by DIC CORPORATION); DOWSIL 8032ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (all manufactured by Dow Corning Toray Co., Ltd.); X-22-4952, KF-643, , KP-109, KP-109, KP-112, KP-120, KP-121, KP-124, KP-125, KP-301, KP-306, KP-310, KP-322, KP-323 , KP-327, KP-341, KP-368, KP-369, KP-611, KP-620, KP-621, KP-626 and KP-652 (the above are Shin-EtsuSilicone Co., Ltd.); F-4440, TSF-4300, TSF-4445, TSF-4460 and TSF-4452 (all manufactured by Momentive Performance Materials Inc.); BYK300, BYK306, BYK307, BYK310, BYK320, BYK323, BYK325, BYK330, BYK313, BYK315N, BYK331, BYK333, BYK345, BYK347, BYK348, BYK349, BYK370, BYK377, BYK378 and BYK323 (all manufactured by BYK Chemie).
[0440] Furthermore, as the surfactant, a nonionic surfactant can also be mentioned.
[0441] The surfactant may be used alone or in combination of two or more.
[0442] The content of the surfactant is preferably 0.01 to 3.0% by mass, more preferably 0.01 to 1.0% by mass, and even more preferably 0.05 to 0.8% by mass, relative to the total solid content of the composition.
[0443] 〔Other additives〕
[0444] The composition may contain other additives in addition to the above-mentioned various components.
[0445] Examples of other additives include heterocyclic compounds (e.g., triazole, benzotriazole, tetrazole, and derivatives thereof), aliphatic thiol compounds, thermally crosslinkable compounds, polymerization inhibitors, hydrogen donating compounds, solvents, impurities, plasticizers, sensitizers, and alkoxysilane compounds.
[0446] Examples of the heterocyclic compound, the aliphatic thiol compound, the thermally crosslinkable compound, the polymerization inhibitor, and the hydrogen donating compound include various components described in International Publication No. 2022 / 039027.
[0447] As the tar enhancer, the sensitizer, and the alkoxysilane compound, for example, paragraphs 0097 to 0119 of International Publication No. 2018 / 179640 can be cited.
[0448] The solvent is not particularly limited as long as it can dissolve or disperse various components that may be contained in the composition other than the solvent.
[0449] Examples of the solvent include water, alkylene glycol ether solvents, alkylene glycol ether acetate solvents, alcohol solvents (e.g., methanol and ethanol), ketone solvents (e.g., acetone and methyl ethyl ketone), aromatic hydrocarbon solvents (e.g., toluene), aprotic polar solvents (e.g., N,N-dimethylformamide), cyclic ether solvents (e.g., tetrahydrofuran), ester solvents (e.g., n-propyl acetate), amide solvents, lactone solvents, and solvents containing two or more thereof.
[0450] The solvent may be used alone or in combination of two or more.
[0451] The content of the solvent is preferably 50 to 1900 parts by mass, more preferably 100 to 1200 parts by mass, and even more preferably 100 to 900 parts by mass, based on 100 parts by mass of the total solid content of the composition.
[0452] The composition may contain impurities.
[0453] As impurities, for example, sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogen and ions thereof can be cited. Halide ions, sodium ions and potassium ions (preferably sodium ions and chloride ions) are easily mixed as impurities, so it is preferably set to the following content.
[0454] The composition does not contain impurities (especially sodium ions or chloride ions), or, when the composition contains impurities, the content of the impurities is 100 mass ppm or less relative to the total solid content of the composition, preferably 80 mass ppm or less, more preferably less than 50 mass ppm, further preferably 10 mass ppm or less, particularly preferably less than 10 mass ppm, and most preferably 2 mass ppm or less. The lower limit is 0 mass ppb or more relative to the total solid content of the composition, preferably 1 mass ppb or more, and more preferably 0.1 mass ppm or more.
[0455] Specific examples of the amount of impurities include a chloride ion concentration of 15 ppm, a bromide ion concentration of 1 ppm, a sodium ion concentration of 5 ppm, and an iron ion concentration of 1 ppm relative to the total solid content of the composition.
[0456] Examples of methods for adjusting the content of impurities include a method of using raw materials with a low impurity content as raw materials for various components that may be included in the composition, a method of purifying various components that may be included in the composition, and a method of preventing impurities from being mixed in when preparing the composition.
[0457] In particular, as a method for adjusting the content of sodium ions and chloride ions, for example, there is a method of surface-treating the filler using a surface-modifying agent having a small content of the surface-modifying agent and a small content of impurities.
[0458] For example, the content of impurities can be quantified by known methods such as ICP (Inductively Coupled Plasma) emission spectrometry, atomic absorption spectrometry, and ion chromatography. When ion chromatography is used, for example, ICS-2100 manufactured by Thermo Fisher is used as an analysis device, and when the object of measurement is an anion, IonPac AS11HC manufactured by Thermo Fisher is used as a column, and when the object of measurement is a cation, IonPac CS12 manufactured by Thermo Fisher is used as a column, and the column temperature can be 35°C for measurement.
[0459] In the composition, preferably, the content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide and hexane is small. Specifically, the content of these compounds is preferably 100 mass ppm or less, more preferably 20 mass ppm or less, and further preferably 4 mass ppm or less, relative to the total solid content of the composition. The lower limit can be 10 mass ppb or more, or 100 mass ppb or more, relative to the total solid content of the composition.
[0460] The content of these compounds can be adjusted by the same method as the above-mentioned impurities, and these compounds can be quantified by a known measurement method.
[0461] It is preferred that a film obtained using the composition exhibits the physical property values described below.
[0462] In particular, a film obtained using the composition of the above-mentioned embodiments Y1 to Y3 preferably shows the [physical property value A] described below, and a film obtained using the composition of embodiments Z1 to Z2 preferably shows the [physical property value B] described below.
[0463] 〔Physical property value A〕
[0464] The average value X of the linear expansion coefficient of the film obtained by method A in the range of 50 to 100° C. is preferably 20 ppm / K or less, more preferably 17 ppm / K or less. The lower limit is preferably 0 ppm / K or more.
[0465] The average value X of the linear expansion coefficient can be measured using TMA (thermomechanical analyzer, manufactured by TA Instruments, TMA450EM). For example, the linear expansion coefficient at each temperature is measured under the measurement conditions of a heating rate of 10°C / min, a chuck spacing of 16mm, a weight of 49mN, and a temperature range of -60 to 350°C, and the average value of the linear expansion coefficient in the range of 50 to 100°C is calculated from the obtained results. The number of tests for the measurement is set to 3, and the arithmetic mean thereof is taken as the average value X.
[0466] In method A, the composition is used to form a composition layer on a substrate, and a high pressure mercury lamp is used at a cumulative illuminance of 100 mJ / cm 2 The composition layer was exposed, and after heat treatment at 230° C. for 8 hours, it was immersed in 2M hydrochloric acid for 8 hours and rinsed with water to obtain a film peeled from the substrate (hereinafter also referred to as “measurement film A”).
[0467] In the above method A, when the measurement membrane A cannot be peeled off from the substrate, the measurement membrane A may be obtained by further immersing the substrate in 2M hydrochloric acid for about one week and performing the above-mentioned rinsing treatment.
[0468] Examples of the substrate in the method A include substrates used in the method for producing a laminated body described later, and a copper substrate is preferred.
[0469] As a method of forming a composition layer using the composition, a method of forming a composition layer in a method of producing a transfer film can be mentioned.
[0470] As a method of a rinsing treatment, a well-known method, such as an immersion treatment and a spray cleaning, is mentioned, for example.
[0471] The water used for the rinsing treatment is preferably pure water. The liquid temperature of the water is preferably room temperature (for example, 20° C.). The time for the rinsing treatment is preferably 10 minutes to 2 hours.
[0472] The exposure may be full-surface exposure or pattern exposure, and full-surface exposure is preferred.
[0473] The ratio of the average linear expansion coefficient Y in the range of 190 to 210°C to the average linear expansion coefficient X of the film obtained by method A in the range of 50 to 100°C (average Y / average X) is preferably 2.0 or less, more preferably 0.9 to 2.0.
[0474] The average value X and its determination method are as described above.
[0475] The average value Y is preferably 40 ppm / K or less, more preferably 15 ppm / K or less. The lower limit is preferably 0 ppm / K or more.
[0476] The method for measuring the average value Y is the same as that for measuring the average value X, except that the temperature range of the calculation object is changed to the range of 190 to 210°C.
[0477] The average relative dielectric constant of the film obtained by method A at 28 GHz is preferably 3.5 or less, more preferably 3.0 or less. The lower limit is not particularly limited, but is often 1.0 or more, and more often 2.0 or more.
[0478] The average relative dielectric constant can be measured, for example, using a Split Cylinder resonator (manufactured by Kanto Electronics Application & Development Inc.) The number of test times for measurement was set to 3, and the arithmetic mean value thereof was defined as the average relative dielectric constant.
[0479] The average dielectric loss tangent at 28 GHz of the film obtained by method A is preferably 0.0030 or less, and more preferably 0.0020 or less. The lower limit is not particularly limited, but is often 0.0001 or more, and even more often 0.0005 or more.
[0480] The average dielectric loss tangent can be measured, for example, using a Split Cylinder resonator (manufactured by Kanto Electronics Application & Development Inc.) The number of test times for the measurement was set to 3, and the arithmetic mean value thereof was defined as the average dielectric loss tangent.
[0481] The above method A is a method of forming a composition layer on a substrate using a composition, but a transfer film may be used instead of the composition to form a composition layer on a substrate.
[0482] As a method of forming a composition layer on a substrate using the transfer film, for example, the transfer method in step X1 can be mentioned.
[0483] 〔Physical property value B〕
[0484] The average value X of the linear expansion coefficient of the film obtained by method B in the range of 50 to 100° C. is preferably 20 ppm / K or less, more preferably 17 ppm / K or less. The lower limit is preferably 0 ppm / K or more.
[0485] The method for measuring the average value X of the linear expansion coefficient is the same as the method for measuring the average value X of the linear expansion coefficient described in the physical property value Y.
[0486] In method B, a composition layer is formed on a substrate using the composition, and the composition layer is heat treated at 230°C for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain a film peeled off from the substrate (hereinafter also referred to as "measurement film B").
[0487] In the above method B, when the membrane B for measurement cannot be peeled off from the substrate, the membrane B for measurement may be obtained by further immersing in 2M hydrochloric acid for about one week and performing the above-mentioned rinsing treatment.
[0488] Examples of the substrate in the method B include substrates used in the method for producing a laminated body described below, and a copper substrate is preferred.
[0489] As a method of forming a composition layer using the composition, a method of forming a composition layer in a method of producing a transfer film can be mentioned.
[0490] As a method of a rinsing treatment, a well-known method, such as an immersion treatment and a spray cleaning, is mentioned, for example.
[0491] The water used for the rinsing treatment is preferably pure water. The liquid temperature of the water is preferably room temperature (for example, 20° C.). The time for the rinsing treatment is preferably 10 minutes to 2 hours.
[0492] The exposure may be full-surface exposure or pattern exposure, and full-surface exposure is preferred.
[0493] The ratio of the average linear expansion coefficient Y in the range of 190 to 210°C to the average linear expansion coefficient X in the range of 50 to 100°C of the film obtained by method B (average Y / average X) is preferably 2.0 or less, more preferably 0.9 to 2.0.
[0494] The average value X and its determination method are as described above.
[0495] The average value Y is preferably 40 ppm / K or less, more preferably 15 ppm / K or less. The lower limit is preferably 0 ppm / K or more.
[0496] The method for measuring the average value Y is the same as that for measuring the average value X, except that the temperature range of the calculation object is changed to the range of 190 to 210°C.
[0497] The average relative dielectric constant of the film obtained by method B at 28 GHz is preferably 3.5 or less, more preferably 3.0 or less. The lower limit is not particularly limited, but is often 1.0 or more, and even more often 2.0 or more.
[0498] The average relative dielectric constant can be measured, for example, using a Split Cylinder resonator (manufactured by Kanto Electronics Application & Development Inc.) The number of test times for measurement was set to 3, and the arithmetic mean value thereof was defined as the average relative dielectric constant.
[0499] The average dielectric loss tangent at 28 GHz of the film obtained by method B is preferably 0.0030 or less, and more preferably 0.0020 or less. The lower limit is not particularly limited, but is often 0.0001 or more, and even more often 0.0005 or more.
[0500] The average dielectric loss tangent can be measured, for example, using a Split Cylinder resonator (manufactured by Kanto Electronics Application & Development Inc.) The number of test times for the measurement was set to 3, and the arithmetic mean value thereof was defined as the average dielectric loss tangent.
[0501] The above method B is a method of forming a composition layer on a substrate using a composition, but a transfer film may be used instead of the composition to form a composition layer on a substrate.
[0502] As a method for forming a composition layer on a substrate using the transfer film, for example, the transfer method in step X1 can be cited.
[0503] [Transfer film]
[0504] The transfer film has a temporary support and a composition layer formed using the above-mentioned composition.
[0505] Figure 2 It is a schematic cross-sectional view showing an example of an embodiment of the transfer film.
[0506] Figure 2 The transfer film 100 shown has a structure in which a temporary support 12, a composition layer 14, and a cover film 16 are stacked in this order.
[0507] Figure 2 The transfer film 100 shown is in a form having the cover film 16, but the transfer film may be in a form not having the cover film 16. Furthermore, as described later, the transfer film may further have an intermediate layer and / or a thermoplastic resin layer.
[0508] Hereinafter, each component included in the transfer film will be described in detail.
[0509] Temporary support
[0510] The transfer film has a temporary support.
[0511] The temporary support is a member that supports the composition layer and is eventually removed by a peeling treatment.
[0512] The temporary support may have a single-layer structure or a multi-layer structure.
[0513] The temporary support is preferably a film, and more preferably a resin film.
[0514] As the temporary support, it is also preferred to have flexibility and not produce significant deformation, shrinkage and elongation under pressure or under pressure and heating. As the above-mentioned film, for example, polyethylene terephthalate film (for example, biaxially stretched polyethylene terephthalate film), polymethyl methacrylate film, cellulose triacetate film, polystyrene film, polyimide film and polycarbonate film can be cited, preferably polyethylene terephthalate film. In addition, the temporary support preferably does not have deformation such as wrinkles and scratches.
[0515] From the viewpoint of being able to carry out pattern exposure across the temporary support, the temporary support preferably has high transparency. Specifically, any transmittance under wavelength 313nm, wavelength 365nm, wavelength 405nm and wavelength 436nm is also preferably 60% or more, more preferably 70% or more, further preferably 80% or more, and most preferably 90% or more. The upper limit is preferably less than 100%. As the preferred value of any transmittance under the above-mentioned wavelengths, for example, 87%, 92% and 98% can be cited.
[0516] From the viewpoint of pattern formation when pattern exposure is performed through a temporary support and the transparency of the temporary support, the haze of the temporary support is preferably small. Specifically, the haze value of the temporary support is preferably 2% or less, more preferably 0.5% or less, and further preferably 0.1% or less. The lower limit is preferably 0% or more.
[0517] From the viewpoint of pattern formation when pattern exposure is performed through a temporary support and the transparency of the temporary support, it is preferred that the number of particles, foreign matter and defects contained in the temporary support is small. The number of particles, foreign matter and defects with a diameter of 1 μm or more in the temporary support is preferably 50 / 10 mm. 2 Below, more preferably 10 / 10mm 2 Below, more preferably 3 / 10mm 2 Below, especially preferably 0 / 10mm 2 .
[0518] The thickness of the temporary support is preferably 5 to 200 μm, more preferably 5 to 150 μm, further preferably 5 to 50 μm, and particularly preferably 5 to 35 μm from the viewpoint of ease of handling and versatility.
[0519] The thickness of the temporary support can be calculated as an average value of five arbitrary points measured by cross-sectional observation using a SEM (scanning electron microscope).
[0520] From the viewpoint of improving the adhesion between the temporary support and the composition layer, the surface of the temporary support in contact with the composition layer may be surface-modified by UV irradiation, corona discharge, plasma, or the like.
[0521] When surface modification is performed by UV irradiation, the exposure amount of UV irradiation is preferably 10 to 2000 mJ / cm 2 , more preferably 50 to 1000 mJ / cm 2 .
[0522] Examples of the light source for UV irradiation include low-pressure mercury lamps, high-pressure mercury lamps, ultrahigh-pressure mercury lamps, carbon arc lamps, metal halide lamps, xenon lamps, chemical lamps, electrodeless discharge lamps, and light-emitting diodes that emit light in a wavelength range of 150 to 450 nm.
[0523] Light output and illumination can be adjusted appropriately.
[0524] As a temporary support, for example, a film thickness of 16 μm can be used. m A biaxially stretched polyethylene terephthalate film having a thickness of 1 μm, a biaxially stretched polyethylene terephthalate film having a film thickness of 12 μm, and a biaxially stretched polyethylene terephthalate film having a film thickness of 9 μm.
[0525] The temporary support may be a recycled product. For example, a product obtained by washing and cutting used films and thinning the obtained materials may be cited as recycled products. For example, a commercially available product of the recycled product may be cited as the Ecouse series (manufactured by TORAY INDUSTRIES, INC.).
[0526] As temporary supports, for example, there can be cited temporary supports described in paragraphs 0017 to 0018 of Japanese Patent Publication No. 2014-085643, paragraphs 0019 to 0026 of Japanese Patent Publication No. 2016-027363, paragraphs 0041 to 0057 of International Publication No. 2012 / 081680, and paragraphs 0029 to 0040 of International Publication No. 2018 / 179370, and the contents of these publications are incorporated into this specification.
[0527] From the viewpoint of imparting handleability, the temporary support may have a layer containing fine particles (lubricant layer) on one or both surfaces of the temporary support. The diameter of the fine particles contained in the lubricant layer is preferably 0.05 to 0.8 μm. The film thickness of the lubricant layer is preferably 0.05 to 1.0 μm.
[0528] Examples of commercially available temporary supports include Lumirror 16FB40, Lumirror 16KS40, Lumirror #38-U48, Lumirror #75-U34, and Lumirror #25T60 (all manufactured by TORAY INDUSTRIES, INC.); COSMOSHINE A4100, COSMOSHINE A4160, COSMOSHINE A4300, COSMOSHINE A4360, and COSMOSHINE A8300 (all manufactured by TOYOBO CO., LTD.).
[0529] 〔Combination layer〕
[0530] The composition layer is a layer formed using the above-mentioned composition.
[0531] Various components that may be contained in the composition layer have the same meanings as, for example, various components that may be contained in the above-mentioned composition, and preferred aspects are also the same.
[0532] The preferred numerical range of the content of each component in the composition layer is the same as the preferred range obtained by rewriting the above-mentioned "content of each component relative to the total solid content (mass %) of the composition" as "content of each component relative to the total mass (mass %) of the composition layer". Specifically, the description "the content of resin X is preferably 5.0% by mass or more relative to the total solid content of the composition" can be rewritten as "the content of resin X is preferably 5.0% by mass or more relative to the total mass of the composition layer".
[0533] From the viewpoints of improving reliability, improving the handling properties of the transfer film, improving lamination properties, etc., the water content of the composition layer is preferably 3.0% by mass or less, more preferably 2.0% by mass or less, and further preferably 1.0% by mass or less relative to the total mass of the composition layer. The lower limit is preferably 0.0001% by mass or more, more preferably 0.01% by mass or more, and more preferably 0.1% by mass or more.
[0534] Specific examples of the water content in the composition layer include 2.5 mass %, 1.5 mass % and 0.3 mass % relative to the total mass of the composition layer.
[0535] From the viewpoints of improving reliability, improving the handling properties of the transfer film, improving lamination properties, etc., the amount of the residual solvent in the composition layer is preferably 6.0% by mass or less, more preferably 4.0% by mass or less, further preferably 2.0% by mass or less, and particularly preferably 1.0% by mass or less, relative to the total mass of the composition layer. The lower limit is preferably 0.0001% by mass or more, more preferably 0.01% by mass or more, and further preferably 0.1% by mass or more.
[0536] Specific examples of the amount of the residual solvent in the composition layer include 3.5 mass %, 2.5 mass %, 1.5 mass % and 0.3 mass % relative to the total mass of the composition layer.
[0537] <Thickness of Composition Layer>
[0538] The average thickness of the composition layer is preferably 0.5 to 40 μm, more preferably 0.5 to 25 μm, and still more preferably 3 to 20 μm. When the average thickness of the composition layer is 40 μm or less, it is preferred in terms of excellent pattern resolution, and when the average thickness of the composition layer is 0.5 μm or more, it is preferred in terms of excellent reliability.
[0539] 〔Middle layer and thermoplastic resin layer〕
[0540] The transfer film may have an intermediate layer and / or a thermoplastic resin layer.
[0541] As the intermediate layer and the thermoplastic resin layer, for example, paragraphs 0164 to 0204 of International Publication No. 2021 / 166719 can be cited, and the contents thereof are incorporated into the present specification.
[0542] From the viewpoint of improving lamination properties, the transfer film preferably has a thermoplastic resin layer, and more preferably has a thermoplastic resin layer between the temporary support and the composition layer.
[0543] <Alkali-soluble resin>
[0544] The thermoplastic resin layer preferably contains an alkali-soluble resin as the thermoplastic resin.
[0545] In the present specification, the term "alkali-soluble" means that the solubility in 100 g of a 1 mass % aqueous solution of sodium carbonate at 22°C is 0.1 g or more.
[0546] As the alkali-soluble resin, for example, acrylic resin, polystyrene resin, styrene-acrylic acid copolymer, polyurethane resin, polyvinyl alcohol, polyvinyl formal, polyamide resin, polyester resin, polyamide resin, epoxy resin, polyacetal resin, polyhydroxystyrene resin, polyimide resin, polybenzoxazole resin, polysiloxane resin, polyethyleneimine, polyallylamine and polyalkylene glycol can be mentioned, and acrylic resin is preferred from the viewpoint of developability and adhesion with adjacent layers. Among them, acrylic resin refers to a resin having at least one structural unit selected from structural units derived from (meth) acrylic acid, structural units derived from (meth) acrylic esters and structural units derived from (meth) acrylic acid amides.
[0547] Furthermore, the alkali-soluble resin is preferably a polymer having an acid group.
[0548] Examples of the acid group include a carboxyl group, a sulfonic acid group, a phosphoric acid group, and a phosphonic acid group, and a carboxyl group is preferred.
[0549] From the viewpoint of developability and adhesion to an adjacent layer, an acrylic resin having a structural unit derived from (meth)acrylic acid is particularly preferred as the alkali-soluble resin.
[0550] The thermoplastic resin layer may contain one kind of alkali-soluble resin alone, or may contain two or more kinds of alkali-soluble resins.
[0551] From the viewpoint of developability and adhesion with adjacent layers, the content of the alkali-soluble resin is preferably 10 to 99% by mass, more preferably 20 to 90% by mass, further preferably 40 to 80% by mass, and particularly preferably 50 to 70% by mass, relative to the total mass of the thermoplastic resin layer.
[0552] The thermoplastic resin layer may contain other components in addition to the alkali-soluble resin.
[0553] Examples of other components include dyes, compounds that generate acids, bases or radicals by light (for example, photoacid generators, photoradical polymerization initiators, photobase generators, etc.), plasticizers, surfactants and sensitizers.
[0554] Specific examples of the various components include the various components described in paragraphs 0164 to 0204 of International Publication No. 2021 / 166719.
[0555] The thickness of the thermoplastic resin layer is not particularly limited, but from the viewpoint of adhesion with the adjacent layer, it is preferably 1 μm or more, more preferably 2 μm or more. The upper limit is not particularly limited, but from the viewpoint of developability and resolution, it is preferably 20 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less.
[0556] 〔Covering film〕
[0557] The transfer film may have a cover film.
[0558] The number of fisheyes with a diameter of 80 μm or more contained in the cover film is preferably 5 / m 2 Fisheyes are foreign matter, undissolved matter, and / or oxidative degradation products of materials that are introduced into the film when the film is produced by methods such as hot melting, kneading, extrusion, and / or biaxial stretching and casting.
[0559] The number of particles with a diameter of 3 μm or more contained in the coating is preferably 30 particles / mm. 2 Below, more preferably 10 / mm 2 Below, more preferably 5 / mm 2 As a result, it is possible to suppress defects caused by the irregularities due to the particles contained in the cover film being transferred to the composition layer.
[0560] The arithmetic mean roughness Ra of the surface of the cover film is preferably 0.01 μm or more, more preferably 0.02 μm or more, and further preferably 0.03 μm or more. If Ra is within such a range, for example, when the transfer film is in a long strip shape, the winding property when the transfer film is wound can be excellent. In addition, from the viewpoint of suppressing defects during transfer, Ra is preferably less than 0.50 μm, more preferably less than 0.40 μm, and further preferably less than 0.30 μm.
[0561] Examples of the cover film include a polyethylene terephthalate film, a polypropylene film, a polystyrene film, and a polycarbonate film.
[0562] Examples of the cover film include the cover films described in paragraphs 0083 to 0087 and 0093 of Japanese Patent Application Laid-Open No. 2006-259138.
[0563] Examples of the cover film include ALFAN (registered trademark) FG-201 (manufactured by Oji F-Tex Co., Ltd.), ALFAN (registered trademark) E-201F (manufactured by Oji F-Tex Co., Ltd.), Cerapeel (registered trademark) 25WZ (manufactured by TORAY ADVANCED FILM CO., LTD.), and Lumirror (registered trademark) 16QS62 (16KS40) (manufactured by TORAY INDUSTRIES, INC.).
[0564] The covering film may be a recycled product. As a recycled product, for example, a product obtained by washing and cutting a used film etc. and forming the obtained material into a film. As a commercially available product of a recycled product, for example, the Ecouse series (manufactured by TORAY INDUSTRIES, INC.) may be cited.
[0565] 〔Other layers〕
[0566] The transfer film may include other layers in addition to the above-mentioned layers.
[0567] As another layer, a high refractive index layer is mentioned, for example.
[0568] As the high refractive index layer, for example, paragraphs 0168 to 0188 of International Publication No. 2021 / 187549 can be cited, and the contents thereof are incorporated into the present specification.
[0569] [Method for producing transfer film]
[0570] A known production method can be applied to the production method of the transfer film.
[0571] The method for producing the transfer film preferably comprises applying the composition on a temporary support to form a composition layer.
[0572] For example, as Figure 2 The method for producing the transfer film 100 shown may include a method including the steps of applying the composition on the surface of a temporary support to form a coating film, and further drying the coating film to form a composition layer.
[0573] Furthermore, a cover film is pressed onto the composition layer of the transfer film produced by the above production method to produce a Figure 2 The transfer film 100 shown in FIG. Figure 2 The transfer film 100 shown is then rolled up and stored as a roll-shaped transfer film 100. The roll-shaped transfer film 100 can be provided as it is to a roll-to-roll method laminating step with a substrate described later.
[0574] Furthermore, as described above, the transfer film may have an intermediate layer and / or a thermoplastic resin layer between the temporary support and the composition layer.
[0575] Examples of the intermediate layer-forming composition, the intermediate layer-forming method, the thermoplastic resin layer-forming composition, and the thermoplastic resin layer-forming method include paragraphs 0133 to 0136 and 0143 to 0144 of International Publication No. 2021 / 033451, and the contents thereof are incorporated herein.
[0576] <Method for Forming Composition Layer>
[0577] As a method for forming the composition layer, a known method can be used, and for example, a method of forming the composition layer by applying the composition and drying the composition can be mentioned.
[0578] As described above, the composition contains the resin X and a predetermined amount of a filler having an average particle size of 300 μm or less.
[0579] Examples of the coating method include slit coating, spin coating, curtain coating, and inkjet coating.
[0580] The composition preferably further comprises a solvent. The solvent has the same meaning as the solvent that may be contained in the above-mentioned composition, and the preferred aspects are also the same.
[0581] [use]
[0582] The pattern (film) obtained from the composition layer formed by using the above composition or the above transfer film can be applied to various applications, for example, electrode protection film, insulating film, planarization film, outer coating film, hard coating film, passivation film, partition wall, spacer, microlens, filter, antireflection film, etching resist and plated parts.
[0583] As more specific examples, there can be cited protective films or insulating films for touch panel electrodes, protective films or insulating films for printed circuit boards, protective films or insulating films for TFT substrates, interlayer insulating films in stacked substrates of semiconductor packages, organic interposers, color filters, outer coatings for color filters, and etching resists for forming wiring, etc.
[0584] [Method for producing laminated body]
[0585] The method for producing the laminate is not particularly limited as long as it is a method using the above-mentioned composition or the above-mentioned transfer film.
[0586] Specifically, the method for producing a laminate preferably includes steps X1 to X3, and more preferably includes steps X1 to X4.
[0587] Step X1: Step of forming a composition layer on a substrate using a composition or a transfer film
[0588] Step X2: Step of pattern-exposing the composition layer
[0589] Step X3: a step of developing the exposed composition layer using a developer (eg, an alkaline developer, an organic solvent developer, etc.) to form a pattern
[0590] Step X4: Step of heating the above pattern
[0591] The developer preferably contains at least one selected from cyclopentanone, an aqueous tetramethylammonium hydroxide solution, an aqueous sodium hydroxide solution, an aqueous sodium carbonate solution, and an aqueous potassium carbonate solution.
[0592] Hereinafter, each step of the method for producing the laminate will be described in detail.
[0593] <Process X1>
[0594] Step X1 is a step of forming a composition layer on a substrate using the composition or the transfer film.
[0595] When a composition is used, step X1 is preferably a step of applying the composition on a substrate to form a composition layer.
[0596] The method for applying the composition may be the method for forming a composition layer in the method for producing the transfer film described above.
[0597] When a transfer film is used, step X1 is preferably a step of bonding the transfer film and the substrate by bringing the surface of the composition layer on the side opposite to the temporary support side in the transfer film into contact with the substrate.
[0598] For lamination, a known laminator such as a laminator, a vacuum laminator, and an automatic cutting laminator can be used.
[0599] Examples of the lamination method include known transfer methods and lamination methods, and a method in which a substrate is placed on the surface of the composition layer and then pressurized and heated with a roller or the like is preferred.
[0600] Examples of the lamination method include well-known laminators such as a vacuum laminator and an automatic cutting laminator.
[0601] The lamination temperature is not particularly limited, but is preferably 70 to 130°C.
[0602] The step X1 is preferably performed by a roll-to-roll method. The substrate to which the transfer film is bonded is preferably a resin film having a resin film or a conductive layer.
[0603] The roll-to-roll method refers to the following method: a substrate that can be rolled up and unrolled is used as the substrate, a process of unwinding the substrate is included before any process included in the method for manufacturing the laminate of the present invention, and a process of winding the substrate is included after any process, and at least any process (preferably all processes or all processes except the heating process) is performed while conveying the substrate.
[0604] As the unwinding method in the unwinding step and the winding method in the winding step, a known method may be used in a production method to which a roll-to-roll system is applied.
[0605] (Base material)
[0606] Examples of the substrate include a glass substrate, a glass epoxy substrate, a silicon substrate, a resin substrate, and a substrate having a conductive layer.
[0607] The refractive index of the substrate is preferably 1.50 to 1.52.
[0608] The substrate may be composed of a light-transmitting substrate such as a glass substrate, and for example, a tempered glass represented by Gorilla Glass of Corning Incorporated may be used. In addition, as the material contained in the above-mentioned substrate, for example, the materials used in Japanese Patent Publication No. 2010-086684, Japanese Patent Publication No. 2010-152809, and Japanese Patent Publication No. 2010-257492 may also be cited.
[0609] When the substrate includes a resin substrate, the resin substrate is preferably a resin film with small optical distortion and / or high transparency, and specifically, polyethylene terephthalate (PET), polyethylene naphthalate, polycarbonate, triacetyl cellulose, cycloolefin polymer, and polyimide.
[0610] As the substrate having a conductive layer, from the viewpoint of production by a roll-to-roll method, a resin substrate having a conductive layer is preferred, and a resin film having a conductive layer is more preferred.
[0611] As the conductive layer, for example, any conductive layer used in general circuit wiring or touch panel wiring can be mentioned.
[0612] As the conductive layer, from the viewpoint of conductivity and fine line formability, it is preferably a layer selected from one or more of a metal layer (for example, a metal foil, etc.), a conductive metal oxide layer, a graphene layer, a carbon nanotube layer and a conductive polymer layer, more preferably a metal layer, and even more preferably a copper layer or a silver layer.
[0613] Furthermore, the conductive layer in the substrate having a conductive layer may be one layer or two or more layers.
[0614] When the substrate having a conductive layer includes two or more conductive layers, it is preferable that the respective conductive layers be made of materials different from each other.
[0615] Examples of the material of the conductive layer include simple metals and conductive metal oxides.
[0616] Examples of the metal element include Al, Zn, Cu, Fe, Ni, Cr, Mo, Ag, and Au.
[0617] As conductive metal oxides, for example, ITO (Indium Tin Oxide), IZO (Indium Zinc Oxide) and SiO2 can be cited. Conductivity means that the volume resistivity is less than 1×10 6 Ωcm, preferably the volume resistivity is less than 1×10 4 Ωcm.
[0618] When the substrate having a conductive layer has two or more conductive layers, at least one of the conductive layers preferably contains a conductive metal oxide.
[0619] <Process X2>
[0620] Step X2 is a step of pattern-exposing the composition layer after the above-mentioned step X1.
[0621] In addition, "pattern exposure" means a method of performing exposure in a pattern, that is, exposure in which exposed portions and unexposed portions exist.
[0622] The positional relationship between the exposed portion and the unexposed portion in pattern exposure is not particularly limited and can be adjusted appropriately.
[0623] The exposure may be performed from the side of the composition layer opposite to the substrate, or from the substrate side of the composition layer.
[0624] The light source used for exposure can be appropriately selected as long as it is a light source that irradiates the various photosensitizable components in the composition layer (for example, photopolymerization initiators and photoacid generators, etc.) with light in a photosensitizable wavelength region (for example, light in a wavelength region such as 254 nm, 313 nm, 365 nm, and 405 nm, etc.).
[0625] Specifically, there can be mentioned an ultra-high pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, and an LED (Light Emitting Diode).
[0626] The exposure dose is preferably 5 to 200 mJ / cm 2 , more preferably 10 to 200 mJ / cm 2 .
[0627] In step X2, pattern exposure can be performed after peeling off the temporary support from the composition layer, or pattern exposure can be performed across the temporary support before peeling off the temporary support, and then the temporary support is peeled off. In order to prevent mask contamination caused by contact between the composition layer and the mask and to avoid the influence of foreign matter attached to the mask on exposure, it is preferred to perform pattern exposure without peeling off the temporary support. In addition, pattern exposure can be exposure across a mask or direct exposure using a laser or the like.
[0628] When exposure is performed through a mask, examples of the mask include a quartz mask, a soda-lime glass mask, and a film mask. A quartz mask is preferred from the viewpoint of excellent dimensional accuracy, and a film mask is preferred from the viewpoint of easy upsizing.
[0629] As a material of a film mask, a polyester film is preferable, and a polyethylene terephthalate film is more preferable. As a material of a film mask, XPR-7S SG (made by FUJIFILM Global Graphic Systems Co., Ltd.) is mentioned, for example.
[0630] In addition, it is preferred that the temporary support be peeled off from the composition layer before step X3 described later.
[0631] <Process X3>
[0632] Step X3 is a step of developing the exposed composition layer using a developer (for example, an alkaline developer and an organic solvent developer) to form a pattern after the above-mentioned step X2.
[0633] Examples of the developer include an alkaline developer and an organic solvent developer.
[0634] The developer preferably contains at least one selected from cyclopentanone, an aqueous tetramethylammonium hydroxide solution, an aqueous sodium hydroxide solution, an aqueous sodium carbonate solution, and an aqueous potassium carbonate solution.
[0635] (Alkaline developer)
[0636] As the alkaline developer, an alkaline aqueous solution is preferred.
[0637] An aqueous alkaline solution-based developer containing a compound having a pKa of 7 to 13 at a concentration of 0.05 to 5 mol / L is preferred.
[0638] The content of water in the alkaline developer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more relative to the total mass of the alkaline developer. The upper limit is preferably less than 100% by mass relative to the total mass of the alkaline developer.
[0639] As the alkaline developer, for example, there can be mentioned an aqueous sodium carbonate solution, an aqueous potassium carbonate solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, and an aqueous tetramethylammonium hydroxide solution. As the concentration of the alkaline developer (the alkali component constituting the alkaline developer), for example, there can be mentioned a 0.1 mass % aqueous solution, a 1.0 mass % aqueous solution, and a 2.38 mass % aqueous solution.
[0640] Furthermore, the alkaline developer may contain a water-soluble organic solvent, a surfactant, etc. Examples of the alkaline developer include the developer described in paragraph 0194 of International Publication No. 2015 / 093271.
[0641] (Organic solvent developer)
[0642] Examples of the organic solvent developer include developers containing organic solvents such as ketone solvents, ester solvents, alcohol solvents, amide solvents, ether solvents, and hydrocarbon solvents.
[0643] Examples of the organic solvent developer include cyclopentanone and propylene glycol monomethyl ether acetate, and cyclopentanone is preferred.
[0644] In the organic solvent developer, the organic solvent may be mixed with multiple types, or may be mixed with organic solvents other than the above or water. The water content of the organic solvent developer is preferably less than 10% by mass, and more preferably substantially free of water, relative to the total mass of the organic solvent developer. The content of the organic solvent in the organic solvent developer is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and most preferably 95% by mass or more, relative to the total mass of the organic solvent developer. The upper limit is preferably 100% by mass or less.
[0645] As a developing method, for example, there can be mentioned spinning immersion development, spray development, rotary development and immersion development. Spray development can remove unnecessary parts by spraying a developer to the exposed composition layer by spraying. In addition, after development, it is also preferred to spray a cleaning agent by spraying, while wiping with a brush or the like to remove the development residue. The liquid temperature of the developer is preferably 20 to 40°C.
[0646] <Process X4>
[0647] The method for producing a laminate preferably includes step 4 after step X3.
[0648] Step X4 is a step of heat-treating the pattern obtained in step X3.
[0649] When the composition contains a polyimide precursor and a polybenzoxazole precursor, the ring-closing reaction of these precursors is promoted in step X4 to produce polyimide and polybenzoxazole.
[0650] Furthermore, by step X4, the purity of the pattern can be improved. The purity of the above-mentioned pattern means that the various components contained in the pattern are substantially only composed of polyimide and polybenzoxazole. Specifically, relative to the total mass of the pattern, the total content of polyimide and polybenzoxazole is preferably 90% by mass or more, more preferably 95% by mass or more. The upper limit is preferably 100% by mass or less.
[0651] For example, the pattern obtained in step X3 may contain a polymer derived from the polymerizable compound generated in step 2. In contrast, if step X4 is performed, it is estimated that the polymer is depolymerized, and the depolymerized product is removed, and further, byproducts generated by the ring-closing reaction of the precursor (for example, compounds generated by decomposition of a part of the groups of the precursor) can also be removed, and as a result, the purity of the pattern can be improved.
[0652] The temperature and time of the heat treatment are not particularly limited as long as they are a temperature and a time that promote the ring-closure reaction of the above-mentioned precursor.
[0653] The temperature of the heat treatment is preferably 120 to 400°C, more preferably 150 to 400°C, and further preferably 190 to 350°C.
[0654] The time for the heat treatment is preferably 1 to 24 hours, more preferably 1 to 12 hours, and even more preferably 1 to 9 hours.
[0655] The heat treatment may be performed in either an air environment or a nitrogen replacement environment.
[0656] The gas pressure in the heat treatment environment is preferably 8.1 kPa or more, more preferably 50.66 kPa or more, and the upper limit is preferably 121.6 kPa or less, more preferably 111.46 kPa or less, and further preferably 101.3 kPa or less.
[0657] 〔Other processes〕
[0658] The method for producing a laminated body may include other steps besides those described above.
[0659] As other steps, for example, the following steps can be mentioned.
[0660] <Cover film peeling step>
[0661] In the method for producing the laminated body, when the transfer film has a cover film, it is preferable to include a step of peeling off the cover film of the transfer film.
[0662] A known method can be applied to the method of peeling off the cover film.
[0663] <Process for reducing visible light reflectivity>
[0664] When the base material is a substrate having a conductive layer, the method for producing a laminate may further include a step of performing a treatment to reduce the visible light reflectance of the conductive layer.
[0665] Furthermore, when the base material is a substrate having a plurality of conductive layers, the treatment for reducing the visible light reflectance may be performed on a part of the conductive layers or on all of the conductive layers.
[0666] As a treatment for reducing the visible light reflectance, an oxidation treatment can be mentioned. For example, by subjecting copper to an oxidation treatment to form copper oxide and turning it black, the visible light reflectance of the conductive layer can be reduced.
[0667] Preferred embodiments of the treatment for reducing the visible light reflectance include the contents described in paragraphs 0017 to 0025 of Japanese Patent Application Laid-Open No. 2014-150118 and paragraphs 0041, 0042, 0048, and 0058 of Japanese Patent Application Laid-Open No. 2013-206315, and these contents are incorporated into this specification.
[0668] <Etching process>
[0669] When the base material is a substrate having a conductive layer, the method for manufacturing the above-mentioned stacked body may include a step (etching step) of using the pattern (film) formed by step X3 or step X4 as an etching resist film and etching the conductive layer in an area where the etching resist film is not configured.
[0670] Examples of the etching method include a wet etching method described in paragraphs 0048 to 0054 of Japanese Patent Application Laid-Open No. 2010-152155 and a dry etching method such as known plasma etching.
[0671] It is also preferable that the method for producing the laminated body uses a substrate having a plurality of conductive layers on both surfaces, and patterning the conductive layers formed on both surfaces sequentially or simultaneously.
[0672] With this structure, the first conductive pattern can be formed on one surface of the substrate, and the second conductive pattern can be formed on the other surface. It is also preferable to form from both sides of the substrate in a roll-to-roll manner.
[0673] [Method for manufacturing circuit wiring]
[0674] The method for producing the circuit wiring is not particularly limited as long as the circuit wiring is produced using a composition or a transfer film.
[0675] Preferably, the method comprises: a step of bonding the transfer film to the substrate having a conductive layer by bringing the surface of the composition layer in the transfer film on the side opposite to the temporary support body into contact with the conductive layer in the substrate having a conductive layer, or a step of coating the composition on the substrate to form a composition layer; a step of exposing the composition layer in a pattern; a step of developing the exposed composition layer with a developer to form a pattern; and a step of etching the conductive layer in an area where no pattern is arranged.
[0676] The method for producing a circuit wiring preferably includes a step of heating the pattern between the step of forming the pattern and the step of etching. As an example of the step of heating, step 4 can be cited.
[0677] As each step in the method for producing a circuit wiring of the present invention, for example, each step in the method for producing a laminated body described above can be cited.
[0678] The method for producing a circuit wiring of the present invention is also preferably a method in which the above-mentioned lamination step or the step of forming a composition layer using the composition to the step of performing an etching treatment is repeated as one set and in a plurality of sets.
[0679] The film used as the etching resist film can also be used as a protective film (insulating film) for the formed circuit wiring.
[0680] [Method for manufacturing semiconductor package]
[0681] As a method for manufacturing a semiconductor package, for example, a known manufacturing method such as a method for manufacturing a stacked substrate can be cited.
[0682] Specifically, there can be mentioned a production method which includes step Z1 to step Z5 in order.
[0683] Step Z1: a step of forming a composition layer on a substrate having a conductive layer using a composition or a transfer film
[0684] Step Z2: Step of pattern-exposing the composition layer
[0685] Step Z3: a step of developing the exposed composition layer using a developer to form a pattern having through holes
[0686] Step Z4: Step of heating the above pattern
[0687] Step Z5: Step of forming a circuit pattern on the above pattern
[0688] As step Z1, step Z2, and step Z4 in the method for manufacturing a semiconductor package, step X1, step X2, and step X4 can be cited, respectively.
[0689] [Process Z3]
[0690] Step Z3 is a step of developing the exposed composition layer using a developer to form a pattern having through holes.
[0691] As a method of performing development using a developer, for example, there can be mentioned a method of performing development using the developer in step X3.
[0692] The shapes of the through holes in the above pattern include, for example, quadrilateral, trapezoid and inverted trapezoid as cross-sectional shapes; and circle and quadrilateral as front shapes (shape of the through hole when viewed from the bottom of the through hole).
[0693] The shape of the through hole in the above pattern is preferably an inverted trapezoidal cross-sectional shape from the viewpoint of improving the adhesion of the plated copper to the wall surface of the through hole.
[0694] The through hole size (diameter) is usually 300 μm or less, preferably 200 μm or less, more preferably less than 40 μm, further preferably 30 μm or less, further preferably 20 μm or less, particularly preferably 10 μm or less, and most preferably 5 μm or less. The lower limit is preferably 1 μm or more, more preferably 5 μm or more.
[0695] The number of the through holes may be 1 or 2 or more, preferably 2 or more.
[0696] 〔Process Z5〕
[0697] Step Z5 is a step of forming a circuit pattern on the above-mentioned pattern.
[0698] As a method for forming a circuit pattern, a semi-additive process is preferred from the viewpoint of being able to form fine wiring.
[0699] As a semi-additive process, first, after the through-hole bottom, through-hole wall surface, and the entire surface of the pattern after the above-mentioned step Z3, electroless copper plating treatment is performed using a palladium catalyst or the like to form a seed layer.
[0700] The seed layer is used to form a power supply layer for electrolytic copper plating, and the thickness of the seed layer is preferably 0.1 to 2.0 μm. If the thickness of the seed layer is 0.1 μm or more, it tends to be able to suppress the reduction of connection reliability during electrolytic copper plating, and if the thickness of the seed layer is 2.0 μm or less, it tends to be unnecessary to increase the etching amount when flash etching the seed layer between wirings, and to suppress damage to the wiring during etching.
[0701] The electroless copper plating treatment is performed by depositing metallic copper on the surface of the pattern having the through-holes by reaction between copper ions and a reducing agent.
[0702] Examples of the electroless plating method and the electrolytic plating method include well-known plating methods.
[0703] As the catalyst for the electroless plating treatment process, a palladium-tin mixed catalyst is preferred. The average primary particle size of the mixed catalyst is preferably 10 nm or less. Furthermore, as the plating composition for the electroless plating treatment process, hypophosphorous acid is preferably included as a reducing agent.
[0704] Examples of commercially available electroless copper plating solutions include "MSK-DK" manufactured by Atotech Japan KK and "SULCUP (registered trademark) PEAver. 4" series manufactured by UEMURA KOGYO CO., LTD.
[0705] Preferably, after the electroless copper plating treatment is performed, the surface of the composition layer of the transfer film on the opposite side to the temporary support is thermally pressed to the electroless copper plated layer using a roll laminator.
[0706] From the viewpoint of being able to make the thickness of the composition layer higher than the wiring height after copper electroplating, the thickness is preferably 5 to 30 μm.
[0707] After the transfer film is thermocompressed, the composition layer is exposed, for example, through a mask on which a desired wiring pattern is drawn. Examples of the exposure method include the exposure method in step X2.
[0708] After exposure, the temporary support of the transfer film is peeled off, and the exposed composition layer is developed using an alkaline developer to form a pattern. After the pattern is formed, the development residue of the composition may be removed using plasma or the like.
[0709] After development, copper electroplating is performed to form a copper circuit layer and fill the through-holes.
[0710] After the copper electroplating, the pattern is removed using an alkaline aqueous solution or an amine-based stripping agent.
[0711] After the pattern is lifted off, the seed layer between the wirings is removed (flash etching).
[0712] Flash etching can be performed using an oxidizing solution including an acidic solution such as sulfuric acid and hydrogen peroxide. Examples of the oxidizing solution include "SAC" manufactured by JCU CORPORATION and "CPE-800" manufactured by Mitsubishi Gas Chemical Company, Inc. After flash etching, palladium and the like attached to the portion between wirings are removed as needed. The removal of palladium can be performed using an acidic solution such as nitric acid and hydrochloric acid.
[0713] It is preferred to perform a post-baking process after pattern stripping or after the flash etching process. In the post-baking process, unreacted thermosetting components are fully thermally cured, thereby improving electrical insulation reliability, curing characteristics, and bonding strength with copper plating.
[0714] As thermal curing conditions, a curing temperature of 150 to 240° C. and a curing time of 15 to 500 minutes are preferred.
[0715] The method for manufacturing a semiconductor package may include a roughening step of roughening the pattern having the through hole. The roughening step is preferably performed after the step Z4 and before the step Z5.
[0716] By performing the roughening step, the pattern surface can be roughened to improve the adhesion with the circuit wiring, and coating unevenness can also be removed at the same time.
[0717] As the roughening step, for example, a known deburring treatment can be mentioned, and a treatment in which a roughening liquid is brought into contact is preferred.
[0718] Examples of the roughening liquid include a roughening liquid containing chromium and sulfuric acid, a roughening liquid containing alkaline permanganate (for example, a sodium permanganate roughening liquid, etc.), sodium fluoride, and a roughening liquid containing chromium and sulfuric acid.
[0719] By repeatedly performing the above steps according to the number of required layers, a semiconductor package can be manufactured. In addition, it is preferable to form a solder resist on the outermost layer.
[0720] [Method for manufacturing touch panel]
[0721] The method for producing a touch panel is not particularly limited as long as it is a method for producing a touch panel using a composition or a transfer film.
[0722] Preferably, the process includes: a process of bonding the transfer film and the substrate having a conductive layer by bringing the surface of the composition layer in the transfer film on the side opposite to the temporary support body into contact with the conductive layer in the substrate having a conductive layer (preferably a patterned conductive layer, specifically, a conductive pattern such as a touch panel electrode pattern or wiring) or a process of coating the composition on the substrate to form a composition layer; a process of pattern-exposing the composition layer; and a process of developing the exposed composition layer with a developer to form a patterned protective film or insulating film of the above-mentioned conductive layer.
[0723] [Method for manufacturing semiconductor device]
[0724] A known manufacturing method can be applied to the manufacturing method of the semiconductor device.
[0725] Specifically, there can be mentioned a method for manufacturing a semiconductor device including the method for manufacturing the above-mentioned laminated body or the method for manufacturing the above-mentioned semiconductor package.
[0726] Examples of semiconductor devices include various semiconductor devices such as semiconductor packages used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes).
[0727] [Semiconductor Package]
[0728] The semiconductor package is not particularly limited as long as it includes a pattern (film) obtained from a composition layer formed using the above composition or the above transfer film.
[0729] The cured film can be used as an insulating film, and can also be used as an organic interposer or insulating film in a so-called stacked substrate.
[0730] Example
[0731] Below, the present invention is further described in detail according to the embodiments. The materials, usage amounts, ratios, processing contents and processing steps etc. shown in the following examples can be appropriately changed without departing from the purpose of the present invention. Therefore, the scope of the present invention should not be interpreted restrictively by the embodiments shown below.
[0732] In the following examples, unless otherwise specified, "parts" and "%" refer to "parts by mass" and "mass %", respectively.
[0733] [Preparation of composition]
[0734] Various components are mixed to form a solid content ratio as shown in the following table, and further diluted to a solid content concentration of 30 mass%, a MEK (methyl ethyl ketone) concentration of 20 mass%, and a NMP (N-methyl pyrrolidone) concentration of 50 mass%, thereby preparing a composition. In addition, when the silicon dioxide is not a slurry (in the case of a powder), the silicon dioxide is dispersed in a 50 mass% MEK solution to form a slurry, and then finally mixed to prepare a composition. In addition, the content of sodium ions and chloride ions in the composition is adjusted using a method for adjusting the content of the above-mentioned impurities as needed.
[0735] 〔Resin〕
[0736] Resins A to F are resins corresponding to the resin X.
[0737] <Resin A>
[0738] 4,4'-oxydiphthalic anhydride (20.0 g, 64.5 mmol, dried at 140°C for 12 hours), 2-hydroxyethyl methacrylate (16.8 g, 129 mmol), hydroquinone (0.05 g), pyridine (20.4 g, 258 mmol) and diethylene glycol dimethyl ether (100 g) were mixed and stirred at 60°C for 18 hours to produce a diester of 4,4'-oxydiphthalic acid and 2-hydroxyethyl methacrylate. The obtained diester was then chlorinated with SOCl2 to obtain a reaction mixture.
[0739] Next, a solution obtained by dissolving 4,4'-diaminodiphenyl ether (11.08 g, 58.7 mmol) in N-methylpyrrolidone (100 mL) was added dropwise to the reaction mixture at -5 to 0°C for 20 minutes. Next, the reaction mixture was reacted at 0°C for 1 hour, and then ethanol (70 g) was added and stirred at room temperature for 1 day. Next, the polyimide precursor was precipitated in 5 L of water, and the water-polyimide precursor mixture was stirred at 5,000 rpm for 15 minutes. The polyimide precursor was filtered out from the above mixture, stirred in 4 L of water for 30 minutes, and filtered again. Next, the obtained polyimide precursor was dried at 45°C under reduced pressure for 3 days to obtain resin A as a polyimide precursor. The weight average molecular weight of resin A was 18,000.
[0740] <Resin B>
[0741] 4,4'-oxydiphthalic dianhydride (ODPA, Mw = 310.22, 77.6g) and diphenyl-3,3',4,4'-tetracarboxylic dianhydride (BPDA, Mw = 294.2, 73.6g) were placed in a 2L separable flask, 2-hydroxyethyl methacrylate (HEMA, 134.0g) and γ-butyrolactone (400mL) were added, and pyridine (79.1g) was further added while stirring at room temperature to obtain a reaction mixture. After the heat generated by the reaction ended, it was naturally cooled to room temperature and further allowed to stand for 16 hours. Then, under ice cooling, a solution obtained by dissolving dicyclohexylcarbodiimide (DCC, 206.3g) in γ-butyrolactone (180mL) was added to the reaction mixture while stirring for 40 minutes. Next, a liquid obtained by suspending 4,4'-oxydiphenylamine (ODA, Mw = 200.24, 93.0g) in γ-butyrolactone (350mL) was added while stirring for 60 minutes. Furthermore, after stirring at room temperature for 2 hours, ethanol (30mL) was added and stirred for 1 hour, and then γ-butyrolactone (400mL) was added. The precipitate generated in the reaction mixture was removed by filtration, thereby obtaining a reaction solution. The obtained reaction solution was added to ethanol (3L) to obtain a precipitate as a crude polymer. The obtained crude polymer was filtered out and dissolved in tetrahydrofuran (1.5L) to obtain a crude polymer solution. The obtained crude polymer solution was purified using an anion exchange resin (AmberliteTM15, manufactured by Organo Corporation) to obtain a polymer solution. The obtained polymer solution was added dropwise to water (28L) to precipitate the polymer, and the obtained precipitate was filtered out and then vacuum dried to obtain a powdery polyimide precursor, namely resin B. The weight average molecular weight (Mw) of the resin B was 22,000. The content of imide groups in the polyimide obtained from the resin B was 27.4% by mass per repeating unit.
[0742] <Resin C>
[0743] 4,4'-diaminodiphenyl ether was used as the diamine, and 4,4'-oxydiphthalic anhydride was used as the dianhydride to obtain a polyimide precursor, namely, a resin C. The weight average molecular weight of the resin C was 15,000.
[0744] <Resin D>
[0745] Resin D, which is a polybenzoxazole precursor, was obtained by using 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane as the diamine and 4,4′-oxybis(benzoyl chloride) as the acid chloride. The weight average molecular weight of Resin D was 15,000.
[0746] <Resin E>
[0747] After obtaining resin D, the phenolic hydroxyl group in resin D was further protected with THF (tetrahydrofuranyl) group to obtain resin E.
[0748] <Resin F>
[0749] After obtaining resin C, the carboxyl group in resin C was further protected with THP (tetrahydropyranyl) group to obtain resin F.
[0750] [Chemical formula 17]
[0751]
[0752] 〔filler〕
[0753] ·YA050C-MJE: Spherical silica slurry, surface treated product, solid content concentration 50 mass% MEK slurry, manufactured by ADMATECHS COMPANY LIMITED
[0754] ·SFP-20M: Silica, surface treated product, manufactured by Denka Company Limited
[0755] ·PMA-ST: Silica (spherical silica slurry), surface treated product, manufactured by Nissan Chemical Corporation
[0756] ·MEK-ST-L: Silica (spherical silica slurry), surface treated product, manufactured by Nissan Chemical Corporation
[0757] ·MEK-AC-5140Z: Silica (spherical silica slurry), surface treated product, manufactured by Nissan Chemical Corporation
[0758] NHM-5N: Silica, surface treated product, manufactured by Tokuyama Corporation
[0759] NHM-3N: Silica, surface treated product, manufactured by Tokuyama Corporation
[0760] ·Y50SP-AM1: Silica (spherical silica slurry), surface treated product, manufactured by ADMATECHS COMPANY LIMITED
[0761] ·Y50SZ-AM1: Silica (spherical silica slurry), surface treated product, manufactured by ADMATECHS COMPANY LIMITED
[0762] NP-5N: Silica, surface treated product, manufactured by Tokuyama Corporation
[0763] Pre-adjusted product A: a filler prepared by the following method.
[0764] 10 g of silica extracted from IPA-ST-ZL (silica dispersion liquid manufactured by Nissan Chemical Corporation, without surface treatment) by centrifugation and filtration was mixed with 39 g of NMP and 1 g of 3-methacryloxypropyltrimethoxysilane, and ultrasonically dispersed while stirring to prepare a preliminary preparation A. The average primary particle size of the obtained preliminary preparation A was confirmed to be 80 nm±10% using a Zetasizer.
[0765] 〔Polymerizable compounds〕
[0766] NK3G: NK ester 3G (bifunctional polyethylene glycol methacrylate), manufactured by Shin-Nakamura Chemical Co., Ltd.
[0767] NK4G: NK Ester 4G (bifunctional polyethylene glycol methacrylate), manufactured by Shin-Nakamura Chemical Co., Ltd.
[0768] DPHA: Dipentaerythritol hexaacrylate, manufactured by Tokyo Chemical Industry Co., Ltd.
[0769] 〔Photopolymerization initiator〕
[0770] ·Oxe01: IRGACURE OXE-01, manufactured by BASF
[0771] ·Oxe02: IRGACURE OXE-02, manufactured by BASF
[0772] Omn819: Omnirad 819, manufactured by IGM Resins BV
[0773] [Thermal alkali generator]
[0774] Compound X (hereinafter, refer to the structural formula)
[0775] [Chemical formula 18]
[0776]
[0777] U-CAT SA506: p-Toluenesulfonate of 1,8-diazabicyclo[5.4.0]undecene-7, manufactured by San-Apro Ltd.
[0778] 〔Surfactant〕
[0779] ·F551A: Megafac (registered trademark) F551A, fluorine-based surfactant, manufactured by DIC Corporation
[0780] ·S-324: Silicone surfactant, manufactured by DIC Corporation
[0781] ·S-506: Silicone surfactant, manufactured by DIC Corporation
[0782] 〔Photoacid generator〕
[0783] PAG1: A compound having an oxime sulfonate structure (hereinafter, refer to the structural formula)
[0784] [Chemical formula 19]
[0785]
[0786] ·CPI-100P: A compound having a sulfonium structure, manufactured by Sanyo Chemical Industries, Ltd.
[0787] [Compound Y]
[0788] ·Ethylene glycol phthalate
[0789] ·Dihexyl phthalate
[0790] · Tributyl o-acetyl citrate
[0791] Benzyl 2-ethylhexyl phthalate
[0792] 〔additive〕
[0793] ·HAT:5-amino-1H-tetrazolyl
[0794] ·ATA: 3-amino-1,2,4-triazole
[0795] 〔other〕
[0796] · ZCR-1569H: comparative compound, acid-modified epoxy acrylate, manufactured by Nippon Kayaku Co., Ltd.
[0797] SC2050-LNF: Silica slurry, surface treated product, manufactured by ADMATECHS COMPANY LIMITED
[0798] 〔Developer〕
[0799] Cyclopentanone
[0800] Na2C03aq.: 1 mass% sodium carbonate aqueous solution
[0801] ·TMAHaq.: 2.38 mass% tetramethylammonium hydroxide aqueous solution
[0802] [Measurement of average particle size]
[0803] The composition of each example and comparative example was applied on a glass substrate and dried to form a coating film having a thickness of 4.0 μm.
[0804] A cross section along the normal direction of the surface of the obtained coating film was cut out and observed using a scanning electron microscope, and the major axes of all fillers observed in a region having a length of 3 μm in the longitudinal direction parallel to the thickness direction of the coating film and a length of 10 μm in the lateral direction orthogonal to the longitudinal direction were measured.
[0805] The above operation was performed at five different locations on the coating film, and the average value (arithmetic mean value) of the major diameters of all the fillers measured by the respective operations was taken as the average particle size of the filler.
[0806] In the compositions of the examples and comparative examples, the average particle size was measured as described above, and then the coating film was heated at 230° C. for 8 hours and then the average particle size was measured in the same manner as described above. The result was the same value as the average particle size before the heat treatment.
[0807] [Surface modifier content]
[0808] Each composition was applied to a substrate in such a manner that the thickness after drying became 10 μm and dried (drying temperature 100°C, drying time 3 minutes) to form a composition layer. Next, the obtained composition layer was dissolved in a mixed solvent of MEK:NMP=1:1. Then, the obtained solution was centrifuged and filtered using a 0.2 μm filter to separate the filler. The obtained filler was dried (drying temperature 100°C, drying time 30 minutes) to obtain 30 mg of filler for measurement. Using a TG-DTA device (TG / DTA7300) manufactured by Hitachi High-Tech Science Corporation, the weight reduction rate of the filler for measurement was measured three times under the conditions of heating from room temperature (10°C / min) to 1000°C in an air atmosphere, and the content of the surface modifier (relative to the total solid content of the composition) was calculated based on these arithmetic mean values.
[0809] [Na + and Cl- Content]
[0810] Each composition (1 g) was dissolved in acetone and then diluted with ultrapure water to prepare acetone:ultrapure water=1:9. The Na content in the supernatant of the solution was measured by ion chromatography. + and Cl - The content of (value relative to the total solid content of the composition). In addition, the analysis device was ICS-2100 manufactured by Thermo Fisher Scientific Inc., and the column, CL - In the case of Na + In the case of , IonPac CS12 manufactured by ThermoFisher Scientific Inc. was used, and the column temperature was set to 35°C.
[0811] [Various measurements and evaluations]
[0812] Regarding the compositions described in Tables 1 to 5 described later, measurement samples were prepared according to the following method X.
[0813] A copper-clad polyimide film (METALLOYAL, manufactured by TORAY INDUSTRIES, INC.) was used as a substrate, and the compositions shown in Tables 1 to 5 were applied and dried on the substrate to obtain a laminate having a composition layer with a thickness of 10.0 μm on the substrate. The obtained laminate was exposed from the side of the composition layer opposite to the substrate side (the cumulative illuminance was 100 mJ / cm2 measured by a high-pressure mercury lamp and an illuminance meter with a wavelength of 365 nm). 2 ), heat treated in an oven (230°C, 8 hours), immersed in 2M hydrochloric acid for 8 hours for stripping treatment, and rinsed (with pure water at room temperature for 1 hour), then stripped from the substrate to obtain a self-supporting film derived from the composition layer. In addition, in the above-mentioned stripping treatment, when the self-supporting film cannot be stripped, it is further immersed in 2M hydrochloric acid for about 1 week to strip. The obtained self-supporting film is cut into long strips as a measurement sample.
[0814] Regarding the compositions described in Table 6 below, measurement samples were prepared according to the following method Y.
[0815] A copper-clad polyimide film (METALLOYAL, manufactured by TORAY INDUSTRIES, INC.) was used as the base material, and the composition shown in Table 6 was coated and dried on the base material to obtain a laminate having a composition layer with a thickness of 10.0 μm on the base material. After heat treatment (230 °C, 8 hours) of the obtained laminate in an oven, it was immersed in 2M hydrochloric acid for 8 hours and subjected to a peeling treatment. After rinsing (with pure water at room temperature for 1 hour), a self-supporting film derived from the composition layer was peeled off from the base material. In addition, in the above peeling treatment, when the self-supporting film could not be peeled off, it was further immersed in 2M hydrochloric acid for about 1 week for peeling. The obtained self-supporting film was cut into strips and used as a measurement sample.
[0816] 〔Coefficient of thermal expansion (CTE)〕
[0817] The measurement sample obtained by Method X or Method Y was processed into 19 mm × 5 mm, and the CTE was measured using a TMA (thermal mechanical analyzer, manufactured by TA Instruments, TMA450EM). In addition, the measurement conditions were set as a heating rate of 10 °C / minute, a chuck distance of 16 mm, and a load of 49 mN. The measurement was performed in the temperature range of -60 to 350 °C. The CTE was set as the average value X (ppm / K) in the range of 50 to 100 °C during heating and the average value Y (ppm / K) in the range of 190 to 210 °C. Three samples were measured, and their average values were used.
[0818] 〔Evaluation criteria for CTE〕
[0819] A: The average value X is 17 ppm / K or less
[0820] B: The average value X exceeds 17 ppm / K and is 20 ppm / K or less
[0821] C: The average value X exceeds 20 ppm / K
[0822] 〔Evaluation criteria for average relative permittivity and average dielectric loss tangent〕
[0823] A: The average value of Y / average value of X is less than 0.9
[0824] B: The average value of Y / average value of X is 0.9 to 2.0
[0825] C: The average value of Y / average value of X exceeds 2.0
[0826] 〔Average relative permittivity and average dielectric loss tangent〕
[0827] The average relative dielectric constant and average dielectric loss tangent were measured for the measurement samples obtained by method X or method Y using a 28 GHz split cylinder resonator (manufactured by Kanto Electronics Application & Development Inc.) Three samples were measured, and the average value thereof was used.
[0828] <Evaluation Criteria for Average Relative Permittivity>
[0829] A: Average relative dielectric constant is less than 3.0
[0830] B: Average relative dielectric constant is more than 3.0 and less than 3.5
[0831] C: Average relative dielectric constant exceeds 3.5
[0832] <Evaluation Criteria for Average Dielectric Loss Tangent>
[0833] A: Average dielectric loss tangent is less than 0.0020
[0834] B: Average dielectric loss tangent exceeds 0.0020 and is less than 0.0030
[0835] C: Average dielectric loss tangent exceeds 0.0030
[0836] 〔Photolithography〕
[0837] The composition shown in the table was applied on glass (Corning glass, 5 cm in length×5 cm in width×1.1 mm in thickness) to a thickness of 10 μm after drying, and dried to form a composition layer.
[0838] A temporary support (PET film, Lumirror 16FB40, thickness 16 μm, manufactured by TORAY INDUSTRIES, INC.) and a photomask were sequentially laminated on the obtained composition layer to obtain a laminate.
[0839] When the compositions listed in Tables 1 to 5 were used, a photomask having a plurality of circular shading portions with diameters of 50 μm and 30 μm and an interval between the shading portions (distance from the center of the circle to the center of the circle) of 150 μm or more was used.
[0840] When the composition described in Table 6 was used, a photomask having a plurality of circular openings of 50 μm and 30 μm in diameter and having an opening spacing (distance from the center of a circle to the center of a circle) of 150 μm or more was used.
[0841] The obtained laminate was pattern-exposed from the side of the photomask opposite to the temporary support using an ultra-high pressure mercury lamp. The cumulative exposure measured with a photometer at a wavelength of 365 nm was 5 mJ / cm 2 Then, the photomask was removed from the stack.
[0842] After exposure, the laminate was left to stand for 30 minutes, the temporary support and the photomask were peeled off from the laminate, and the developer shown in the table was used to develop at room temperature for 90 seconds. After development, the laminate was rinsed with a rinse solution for 20 seconds at room temperature, and air was further blown in to remove the residual rinse solution. In addition, as the rinse solution, water was used when the developer was an aqueous solution, and propylene glycol monoethyl ether acetate was used when the developer was an organic solvent. The through holes of each diameter in the developed sample were observed and evaluated according to the following evaluation criteria.
[0843] <Evaluation Criteria for Photolithography (50 μm Diameter)>
[0844] A: A through hole with a diameter of 50 μm or less can be formed, the film is not reduced, and there is no residue at the bottom of the through hole.
[0845] B: Through holes with a diameter of 50 μm or less can be formed, and the film is not reduced, but residues are present at a part of the bottom of the through hole.
[0846] C: A through hole with a diameter of 50 μm or less can be formed, a film reduction of 5% or more and less than 10% with respect to the thickness of the composition layer occurs, and a residue remains at a part of the bottom of the through hole.
[0847] D: A through hole having a diameter of 50 μm or less could not be formed (including a case where there was no photosensitivity and evaluation could not be performed).
[0848] <Evaluation Criteria for Photolithography (Diameter 30 μm)>
[0849] A: A through hole with a diameter of 30 μm or less can be formed, the film is not reduced, and there is no residue at the bottom of the through hole.
[0850] B: Through holes with a diameter of 30 μm or less can be formed, and the film is not reduced, but residues are present at a part of the bottom of the through hole.
[0851] C: A through hole with a diameter of 30 μm or less can be formed, a film reduction of 5% or more and less than 10% with respect to the thickness of the composition layer occurs, and a residue remains at a part of the bottom of the through hole.
[0852] D: A through hole having a diameter of 30 μm or less could not be formed (including a case where there was no photosensitivity and evaluation could not be performed).
[0853] 〔Cyclic thermal characteristics〕
[0854] On a silicon wafer substrate, the composition was applied so that the thickness of the composition layer on the copper pattern became 10 μm and dried to form a composition layer, which formed a 4 μm thick copper pattern in comb-shaped wiring (line / space = 10 μm / 10 μm).
[0855] Next, when the compositions listed in Tables 1 to 5 were used, the resulting composition layer was exposed using an ultra-high pressure mercury lamp. At this time, the cumulative exposure measured by a photometer at a wavelength of 365 nm was 5 mJ / cm 2 After the exposure, a heat treatment was performed at 230° C. for 180 minutes to prepare a sample for evaluation.
[0856] Furthermore, when the composition described in Table 6 was used, the obtained composition layer was subjected to a heat treatment at 230° C. for 180 minutes to prepare a sample for evaluation.
[0857] The evaluation sample was placed in a gas phase at -45°C and 160°C for 30 minutes each using a gas phase thermal tester. This was considered one cycle and after 100 cycles, the number of cracks in a 5 cm × 5 cm area of the evaluation sample was observed and evaluated according to the following criteria.
[0858] <Evaluation Criteria for Cyclic Thermal Characteristics>
[0859] A: No more than 3 cracks
[0860] B: More than 3 and less than 10 cracks
[0861] C: More than 10 and less than 20 cracks
[0862] D: More than 20 cracks
[0863] [Migration resistance]
[0864] On a silicon wafer substrate, each composition was applied so that the thickness of the composition layer on the copper pattern became 10 μm and dried to form a composition layer, which formed a 2.5 μm thick copper pattern in comb-shaped wiring (line / space = 10 μm / 10 μm).
[0865] Next, when the compositions described in Examples 1 to 100, 1-101, 1-102, 1-103 and Comparative Example 1 were used, the resulting composition layer was exposed using an ultra-high pressure mercury lamp. At this time, the cumulative exposure measured by a photometer at a wavelength of 365 nm was 100 mJ / cm 2 After the exposure, a heat treatment was performed at 230° C. for 180 minutes in a nitrogen atmosphere to prepare a sample for evaluation.
[0866] Furthermore, when the compositions described in Examples 101 to 136 were used, the obtained composition layers were heat-treated at 230° C. for 180 minutes in a nitrogen atmosphere to prepare samples for evaluation.
[0867] The samples for evaluation were placed in a 130°C 85% RH (relative humidity) room using a HAST tester, and the time it took for migration to occur when a voltage of 15 V was applied was measured. In addition, the initial resistance value of 1×10 14 For samples with a resistance value of 1×10 3 The time when the migration occurs below Ω.
[0868] <Evaluation Criteria for Migration Resistance>
[0869] A: Migration occurred or did not occur over 72 hours.
[0870] B: Migration occurred within 24 hours or more and within 72 hours.
[0871] C: Migration occurred in less than 24 hours.
[0872] The contents of various components and evaluation results are shown below.
[0873] The column "Content in solid content" shows the solid content concentration (mass %) of each component relative to the total solid content in the composition.
[0874] The column "e / a" indicates the mass ratio of the content of the thermal base generator to the content of the resin X.
[0875] The column "Developing solution for lithography evaluation" shows the developing solution used for lithography evaluation.
[0876] The column "content of surface modifier" shows the content (mass %) of the surface modifier relative to the total mass of the filler.
[0877] “Na + The column "Content (ppm by mass)" shows the content (ppm by mass) of sodium ions relative to the total solid content in the composition.
[0878] “CL - The column "Content (ppm by mass)" shows the content (ppm by mass) of chloride ions relative to the total solid content in the composition.
[0879]
[0880]
[0881]
[0882]
[0883]
[0884] From the evaluation results shown in the table, it was confirmed that the composition of the present invention can obtain the desired effect.
[0885] It was confirmed that when the content of the filler was 60% by mass or more (preferably 70% by mass or more) based on the total solid content of the composition, the effects of the present invention and the like were more excellent (Examples 1 to 6).
[0886] It was confirmed that when the average particle size of the filler was 5 to 100 nm, the effects of the present invention and the like were more excellent (Examples 1, 7, and 9 to 11, and Examples 101 and 104 to 107).
[0887] It was confirmed that when the resin X had a polymerizable group or the resin X contained a precursor having a group that decomposed by an acid to generate a polar group, the photolithography property (diameter 30 μm) was more excellent (Examples 1, 24, 36 and 42, and Examples 101 and 114).
[0888] It was confirmed that when the composition further contained a polymerizable compound, the photolithography properties (diameter 50 μm and diameter 30 μm) were more excellent (Examples 1, 2, 48, and 49).
[0889] It was confirmed that when the content of the surface modifier was 3% by mass or less relative to the total mass of the filler, the photolithography (diameter 50 μm and diameter 30 μm), cycle thermal characteristics and migration resistance were more excellent (Example 1, etc. and Example 1-103). In addition, it was confirmed that when the content of the surface modifier was 1% by mass or less relative to the total mass of the filler, the migration resistance was more excellent (Example 12, and Examples 9 to 11 and 13 to 15).
[0890] In each example, the composition layer was formed on the substrate using the transfer film prepared in the following steps instead of using the composition to form the composition layer, and the same evaluation as the above composition was performed. As a result, the same evaluation results as the composition were obtained.
[0891] The composition shown in the table was applied onto a temporary support (PET film, Lumirror 16FB40, thickness 16 μm, manufactured by TORAY INDUSTRIES, INC.) and dried to form a composition layer having a thickness of 10.0 μm.
[0892] Next, a cover film (polypropylene film, FG-201, thickness 30 μm, manufactured by OjiF-Tex Co., Ltd.) was provided on the composition layer to obtain a transfer film.
[0893] The cover film was peeled off from the transfer film obtained above, and the exposed composition layer was laminated on the substrate in various evaluations to form a composition layer. Lamination was performed using a vacuum laminator (manufactured by MCK) at a substrate temperature of 40°C, a rubber roller temperature of 100°C, a linear pressure of 3N / cm, and a conveying speed of 2m / min. Next, the temporary support was peeled off from the obtained sample. Then, various evaluations were performed in the same steps as the above composition, and the results were the same.
[0894] In each example, a transfer film having a thermoplastic resin layer prepared in the following steps was used to form a composition layer on a substrate instead of using the composition to form a composition layer, and the same evaluation results as the composition were obtained.
[0895] [Method for producing a transfer film having a thermoplastic resin layer]
[0896] A thermoplastic resin layer forming composition "Cu-1" having the structure shown below was applied to a temporary support (PET film, Lumirror 16FB40, thickness 16um, TORAY) and dried to form a thermoplastic resin layer with a thickness of 5μm. Next, the composition described in each embodiment was applied to a covering film (polypropylene, FG-201, thickness 30μm, Oji F-Tex Co., Ltd.) and dried to form a composition layer with a thickness of 10μm. Using a vacuum laminator (manufactured by MCK), the thermoplastic resin layer on the temporary support and the composition layer on the covering film were bonded under the conditions of a substrate temperature of 30°C, a rubber roller temperature of 50°C, a linear pressure of 3N / cm, and a conveying speed of 2m / min, thereby producing a transfer film having a thermoplastic resin layer composed of a temporary support / thermoplastic resin layer / composition layer / covering film.
[0897] The same evaluation results were obtained when the thermoplastic resin layer-forming composition "Cu-1" was changed to the thermoplastic resin layer-forming composition "Cu-2".
[0898] [Table 7]
[0899]
[0900] A-2: A polymer-containing solution containing 40% by mass of a polymer (benzyl methacrylate / methacrylic acid / acrylic acid copolymer (composition ratio of constituent units derived from each monomer in the polymer: 75% by mass / 10% by mass / 15% by mass, weight average molecular weight: 30,000, Tg: 75°C, acid value: 186 mgKOH / g))
[0901] A-11: methyl methacrylate / 2-ethylhexyl acrylate / benzyl methacrylate / methacrylic acid copolymer (composition ratio of constituent units derived from each monomer in the polymer: 55 mol% / 11.7 mol% / 4.5 mol% / 28.8 mol%, weight average molecular weight: 100,000)
[0902] A-12: Styrene / acrylic acid copolymer (composition ratio of constituent units derived from each monomer in the polymer: 63 mol% / 37 mol%, weight average molecular weight: 10,000)
[0903] B-1: A compound having the structure shown below (a dye that develops color when exposed to acid)
[0904] [Chemical formula 20]
[0905]
[0906] C-1: A compound having the structure shown below (photoacid generator, synthesized according to the following method.)
[0907] [Chemical formula 21]
[0908]
[0909] (Synthesis of Compound C-1)
[0910] Aluminum chloride (10.6 g) and 2-chloropropionyl chloride (10.1 g) were added to a suspension of 2-naphthol (10 g) and chlorobenzene (30 mL), and the mixture was heated to 40°C and reacted for 2 hours. Under ice cooling, 4N HCl aqueous solution (60 mL) was added dropwise to the reaction solution, and ethyl acetate (50 mL) was added for separation. Potassium carbonate (19.2 g) was added to the organic layer, and after reacting at 40°C for 1 hour, 2N HCl aqueous solution (60 mL) was added for separation. After concentrating the organic layer, the crystals were re-slurried with diisopropyl ether (10 mL), filtered and dried to obtain a ketone compound (6.5 g).
[0911] To a suspension of the obtained ketone compound (3.0 g) and methanol (18 mL) were added acetic acid (7.3 g) and a 50% by mass hydroxylamine aqueous solution (8.0 g), and the mixture was heated under reflux for 10 hours. After natural cooling, water (50 mL) was added, and the precipitated crystals were filtered, washed with cold methanol, and then dried to obtain an oxime compound (2.4 g).
[0912] The obtained oxime compound (1.8 g) was dissolved in acetone (20 mL), triethylamine (1.5 g) and p-toluenesulfonyl chloride (2.4 g) were added under ice cooling, and the mixture was heated to room temperature and reacted for 1 hour. Water (50 mL) was added to the reaction solution, and the precipitated crystals were filtered, then re-slurried with methanol (20 mL), filtered and dried to obtain C-1 (2.3 g).
[0913] D-3: NK Ester A-DCP (Tricyclodecane dimethanol diacrylate, SHIN-NAKAMURA CHEMICAL CO. LTD.)
[0914] ·D-4: 8UX-015A (multifunctional urethane acrylate compound, Taisei Fine Chemical Co., Ltd.)
[0915] D-5: ARONIX TO-2349 (multifunctional acrylate compound having a carboxyl group, TOAGOSEIC0..LTD.)
[0916] ·D-6: 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane (SHIN-NAKAMURA CHEMICAL Co., Ltd.)
[0917] ·E-1: S-506 (DIC Corporation, Si-based surfactant)
[0918] ·F-1: Phenothiazine (FUJIFILM Wako Pure Chemical Corporation)
[0919] ·F-2: CBT-1 (J0H0KU CHEMICAL C0., LTD)
[0920] MEK: Methyl Ethyl Ketone
[0921] PGME: Propylene glycol monomethyl ether
[0922] ·PGMEA: Propylene glycol monomethyl ether acetate
[0923] Me0H: methanol
[0924] The composition of each embodiment obtained by the above method was applied to a glass epoxy substrate (CCL-EL190T, thickness 1.0 mm, manufactured by Mitsubishi Gas Chemical Company, Inc.) having a circuit pattern formed thereon using a rod coater and dried to form a composition layer on one side of the glass epoxy substrate. The same operation was performed on the back side of the coated surface to form a composition layer on both sides. At this time, the thickness of the composition layer formed on each single side of the glass epoxy substrate was 25 μm.
[0925] After forming a pattern of through holes with a diameter of φ60 μm at a predetermined position on the composition layer and performing a heat treatment, a sodium permanganate aqueous solution was used as a roughening solution to remove residues, and an electroless plating treatment was performed. Next, a resist pattern was formed at a predetermined position using a known dry film resist, and an electrolytic plating treatment was performed. Next, the resist pattern was stripped using a stripping solution. Finally, copper wiring was formed on the cured film by performing a heat treatment (200° C., 3 hours) after performing a seed layer etching treatment.
[0926] The steps from forming the above composition to heat treatment were performed three times in total, and finally a solder resist was formed as the outermost layer, and then a semiconductor element was sealed and mounted, thereby manufacturing a semiconductor package. The obtained semiconductor package was mounted on a predetermined position of a printed wiring board to obtain a semiconductor package substrate. It was confirmed that the obtained semiconductor package substrate was operating normally.
[0927] The cover film was peeled off from the transfer film (transfer film without thermoplastic resin layer) of each example obtained by the above method, and the exposed composition layer was laminated on each single side of a glass epoxy substrate (CCL-EL190T, thickness 1.0 mm, manufactured by Mitsubishi Gas Chemical Company, Inc.) having a circuit pattern formed thereon, and the composition layer was formed on both sides of the glass epoxy substrate. Lamination was performed using a vacuum laminator (manufactured by MCK) at a substrate temperature of 40°C, a rubber roller temperature of 100°C, a linear pressure of 3N / cm, and a conveying speed of 2m / min. Next, the temporary support was peeled off from the obtained sample.
[0928] After forming a pattern of through holes with a diameter of φ50 μm at a predetermined position on the composition layer and performing a heat treatment, a sodium permanganate aqueous solution was used as a roughening solution to remove residues, and an electroless plating treatment was performed. Next, a resist pattern was formed at a predetermined position using a known dry film resist, and an electrolytic plating treatment was performed. Next, the resist pattern was stripped using a stripping solution. Finally, copper wiring was formed on the cured film by performing a heat treatment (200° C., 3 hours) after performing a seed layer etching treatment.
[0929] The above-mentioned lamination to heat treatment steps were performed three times in total, and finally a solder resist was formed as the outermost layer, and then the semiconductor element was sealed and mounted, thereby manufacturing a semiconductor package. The obtained semiconductor package was mounted on a predetermined position of a printed wiring board to obtain a semiconductor package substrate. It was confirmed that the obtained semiconductor package substrate was operating normally.
[0930] Explanation of symbols
[0931] 12 - temporary support, 14 - composition layer, 16 - cover film, 100 - transfer film.
Claims
1. A composition comprising a resin X and a filler, wherein the resin X comprises at least one selected from a polyimide precursor, a polyimide, a polybenzoxazole precursor and a polybenzoxazole, The content of the filler is 50.0% by mass or more relative to the total solid content of the composition, The average particle size of the filler calculated by the following particle size measurement method is 300 nm or less, Particle size measurement method: The composition is applied on a substrate to form a coating film, and a 3μm×10μm rectangular area in a cross section along the normal direction of the surface of the coating film is observed using a scanning electron microscope. The long diameters of all the fillers observed in the area are measured at 5 different locations on the coating film, and the average value of the long diameters of all the fillers measured by each operation is taken as the average particle size of the filler.
2. The composition according to claim 1, wherein The filler comprises at least one selected from silicon dioxide, boron nitride, barium sulfate and silicate.
3. The composition according to claim 1, wherein The average particle size of the filler is 5nm to 100nm.
4. The composition according to claim 1, wherein The content of the filler is 60.0% by mass or more based on the total solid content of the composition.
5. The composition according to claim 1, wherein The filler is surface treated with a surface modifier.
6. The composition according to claim 5, wherein The content of the surface modifier is 3% by mass or less relative to the total mass of the filler.
7. The composition according to claim 6, wherein The content of the surface modifier is 1% by mass or less relative to the total mass of the filler.
8. The composition according to claim 1, further comprising a thermal base generator, The resin X contains the precursor.
9. The composition according to claim 8, wherein The mass ratio of the content of the thermal base generator to the content of the resin X is 0.10 or less.
10. The composition according to claim 8, wherein The content of the thermal base generator is 5.0% by mass or less based on the total solid content of the composition.
11. The composition according to claim 1, wherein In the case where the resin X has a polymerizable group, the composition further comprises a photopolymerization initiator. When the resin X does not have a polymerizable group, the composition further includes a polymerizable compound and a photopolymerization initiator.
12. The composition according to claim 1, further comprising a polymerizable compound.
13. The composition according to claim 12, wherein The content of the polymerizable compound is 25.0% by mass or less based on the total solid content of the composition. 14 . The composition according to claim 1 , further comprising a compound Y having no ethylenically polymerizable group and having a boiling point of 300° C. or higher.
15. The composition according to claim 14, further comprising a polymerizable compound and the compound Y, The total content of the polymerizable compound and the compound Y is 30.0% by mass or less based on the total solid content of the composition.
16. The composition according to claim 11, wherein The content of the photopolymerization initiator is 5.0% by mass or less based on the total solid content of the composition.
17. The composition according to claim 1, wherein Furthermore, no sodium ions are contained, or, when the sodium ions are contained, the content of the sodium ions is less than 50 ppm by mass based on the total solid content of the composition.
18. The composition according to claim 1, wherein The composition further contains no chloride ions, or, When the composition contains the chloride ions, the content of the chloride ions is less than 50 ppm by mass based on the total solid content of the composition.
19. The composition according to claim 11, wherein The average value X of the linear expansion coefficient of the film obtained by method A in the range of 50°C to 100°C is 20 ppm / K or less. Method A: Using the composition to form a composition layer on a substrate, using a high pressure mercury lamp with a cumulative illumination of 100 mJ / cm 2 The composition layer was exposed, and the exposed composition layer was heat-treated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
20. The composition according to claim 11, wherein The ratio of the average value Y of the linear expansion coefficient of the film obtained by method A in the range of 190°C to 210°C to the average value X of the linear expansion coefficient of the film in the range of 50°C to 100°C is 2.0 or less, Method A: Using the composition to form a composition layer on a substrate, using a high pressure mercury lamp with a cumulative illumination of 100 mJ / cm 2 The composition layer was exposed, and the exposed composition layer was heat-treated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
21. The composition according to claim 11, wherein The average relative dielectric constant of the film obtained by method A at 28 GHz is 3.5 or less. Method A: Using the composition to form a composition layer on a substrate, using a high pressure mercury lamp with a cumulative illumination of 100 mJ / cm 2 The composition layer was exposed, and the exposed composition layer was heat-treated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
22. The composition according to claim 11, wherein The average dielectric loss tangent of the film obtained by method A at 28 GHz is 0.0030 or less. Method A: Using the composition to form a composition layer on a substrate, using a high pressure mercury lamp with a cumulative illumination of 100 mJ / cm 2 The composition layer was exposed, and the exposed composition layer was heat-treated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
23. The composition according to claim 1, further comprising a photoacid generator, The resin X includes the precursor having a group that is decomposed by the action of an acid to generate a polar group.
24. The composition according to claim 23, wherein The content of the photoacid generator is 5.0% by mass or less based on the total solid content of the composition.
25. The composition according to claim 23, wherein The average value X of the linear expansion coefficient of the film obtained by method B in the range of 50°C to 100°C is 20 ppm / K or less. Method B: The composition layer is formed on a substrate using the composition, the composition layer is heated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
26. The composition according to claim 23, wherein The ratio of the average value Y of the linear expansion coefficient of the film obtained by method B in the range of 190°C to 210°C to the average value X of the linear expansion coefficient of the film in the range of 50°C to 100°C is 2.0 or less, Method B: The composition layer is formed on a substrate using the composition, the composition layer is heated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
27. The composition according to claim 23, wherein The average relative dielectric constant of the film obtained by method B at 28 GHz is 3.5 or less. Method B: The composition layer is formed on a substrate using the composition, the composition layer is heated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate.
28. The composition according to claim 23, wherein The average dielectric loss tangent of the film obtained by method B at 28 GHz is less than 0.0030. Method B: The composition layer is formed on a substrate using the composition, the composition layer is heated at 230° C. for 8 hours, immersed in 2M hydrochloric acid for 8 hours, and rinsed with water to obtain the film peeled from the substrate. 29 . A transfer film comprising a temporary support and a composition layer formed using the composition according to claim 1 .
30. A method for manufacturing a laminate, comprising the following steps: Using the composition according to any one of claims 1 to 28 to form a composition layer on a substrate; exposing the composition layer to pattern exposure; and The exposed composition layer is developed using a developer to form a pattern, The developer includes at least one selected from cyclopentanone, tetramethylammonium hydroxide aqueous solution, sodium hydroxide aqueous solution, sodium carbonate aqueous solution and potassium carbonate aqueous solution.
31. A method for manufacturing a laminate, comprising the following steps: Using the transfer film according to claim 29 to form a composition layer on a substrate; exposing the composition layer to pattern exposure; and The exposed composition layer is developed using a developer to form a pattern, The developer includes at least one selected from cyclopentanone, tetramethylammonium hydroxide aqueous solution, sodium hydroxide aqueous solution, sodium carbonate aqueous solution and potassium carbonate aqueous solution.
32. A laminated body produced by the method for producing a laminated body according to claim 30.
33. A laminated body produced by the method for producing a laminated body according to claim 31. 34 . A method for manufacturing a semiconductor package, comprising the method for manufacturing a laminate according to claim 30 .
Citation Information
Patent Citations
Optical switch device
JP1989140133A
Phase redistribution processing
JP1992502784A
Photosensitive transferring material, color filter and method for manufacturing the same, liquid crystal display device
JP2006259138A
Polymerizable composition, color filter and method for manufacturing the same, and liquid crystal display
JP2009237362A
Optical thin film with transparent conductive wiring film
JP2010086684A